Model predictive control with state estimation and reduced-order physics for nuclear reactor operation during unanticipated communication transients - Zachery Dahm; Konstantinos Vasili; Vasileios Theos; Linyu Lin; Joe Oncken; Robert England; Vivek Agarwal; Stylianos Chatzidakis (Annals of Nuclear Energy, 2027)

Toward improved conservation risk assessments in the marine aquarium fish trade: Reply to Biondo and Calado (2026) - Bing Lin; Andrew L. Rhyne; Michael Tlusty; Yiwen Zeng; Bryan To; Robert J. Holmberg; David S. Wilcove (Conservation Biology, 2026)

Suppressed upwelling during the Cambrian–Ordovician transition revealed by coupled Cr–Cd isotope systematics - Guoqiang Luan; Karem Azmy; Robert Frei; Chengyan Lin; Jianli Lin; Guangyou Zhu (Geochimica et Cosmochimica Acta, 2026)

Mechanistic characterization of insecticidal Shiva toxin interactions with Drosophila melanogaster nicotinic acetylcholine receptors - Kyle D. Schneider; Joseph Tourtois; Daniel Bertrand; Kumiko Kambara; Daniel Hulbert; Alexandra Haase; Sophia R. Kanniainen; Brian DeVree; Robert M. Kennedy; Lin Bao (Pesticide Biochemistry and Physiology, 2026)

Palaeopolyploidy promoted ancient adaptation of Tibetan sclerophyllous oaks to aridity and cold triggered by mountain uplift - Jin-Jin Hu; Wen-Guang Sun; Jia Liu; Robert A. Spicer; Zhuo Zhou; Yong-Jiang Huang; Zhi-Min Li; Tao Su; Ting-Shen Han; He Tang; Lin-Bo Jia; Yun-Heng Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

The art of interdigitation: Current views on pavement cell shape acquisition - Loitongbam Lorinda Devi; Vinod Kumar; Hemamshu Ratnakaram; Mengzhuo Lin; Stéphanie Robert (Current Opinion in Plant Biology, 2026)

Corrigendum to “In vitro formation and growth of glycogen: experimental verification of theoretical predictions” [Carbohydrate Polymers (2025) 124148] - Xin Liu; Ziyi Wang; Xin Lin; Wang Xu; Mitchell A. Sullivan; Robert G. Gilbert (Carbohydrate Polymers, 2026)

Assessing Potential Data Sources for Landscape-scale Terrestrial Biodiversity Indicators - Tom Bradfer-Lawrence; Meriel Harrison; Adham Ashton-Butt; Sophie Bennett; Robin J. Boyd; Ella Browning; Graeme Buchanan; Adam Fraser; Sian E. Green; Robert Hawkes; Becky E. Heath; Pen-Yuan Hsing; et al. (Environmental Management, 2026)

Feasibility of home-based, remotely delivered exercise training to improve physical function in older sepsis survivors: a pilot randomized controlled trial - Yi Lin; Rola S. Zeidan; Rezvan Ghaderpanah; Margaret K. Ohama; Min-Han Jung; Naveen Baskaran; Juan Sarmiento Delgado; Stephen D. Anton; Barbara K. Smith; Christiaan Leeuwenburgh; Fang-Chi Hsu; Philip A. Efron; et al. (GeroScience, 2026)
Sepsis survivors frequently experience post-discharge physical function decline and encounter logistical barriers to participation in traditional outpatient rehabilitation. This pilot study examined the feasibility, safety, and preliminary efficacy of a remotely delivered, home-based exercise program on physical function in older sepsis survivors. In this single-blinded, randomized controlled trial (RCT), sepsis survivors aged ≥ 55 years were randomized to (a) 12 weeks of avatar-guided, progressive exercise training group (EX) or (b) a standard care control group (CO). Primary outcomes were feasibility (retention, adherence) and safety (adverse events), whereas secondary outcomes were changes in the 30-s Sit-to-Stand (30SSTS), 4-Stage Balance Test (4SBT), Timed Up-and-Go (TUG) tests, and Eastern Cooperative Oncology Group/Zubrod's (ECOG/Zubrod) performance status score. Twenty-one participants were randomized to either EX ( n = 10, mean age = 69.6 ± 8.5 years, 40% females) or CO ( n = 11, mean age = 72.3 ± 7.9 years, 45% females). Mean retention was 95% and adherence to exercise training was 76%. Thirty-four adverse events (AEs) occurred (EX = 11; CO = 16; consented but not randomized = 7 events), including four serious AEs that were unrelated to the study. The EX group showed trends toward improvements in lower-extremity strength (30SSTS: 1.14 ± 2.91 repetitions, Cohen’s d = 0.393) and balance (4SBT: 5.07 ± 4.75 s, d = 1.07), whereas the CO group showed no change in balance on the 4SBT (0.01 ± 4.38 s, d = 0.003) and trends toward decline in lower-extremity strength on the 30SSTS (− 0.88 ± 0.99 repetitions, d = − 0.883). TUG performance showed modest trends toward reductions in completion time in both groups (EX: − 1.42 ± 6.58 s, d = − 0.216; CO: − 1.27 ± 2.73 s, d = − 0.466). ECOG/Zubrod scores showed a modest trend toward improvement in the EX group subset. This pilot RCT demonstrated that a 12-week, remotely delivered exercise program was safe and feasible for older sepsis survivors and showed preliminary signals of positive change in lower-extremity strength, balance, and functional status, which warrants testing efficacy in an adequately powered Phase IIb RCT. ClinicalTrials.gov NCT05568511.

Experimentally derived buoyancy duration of seagrass fragments for biophysical dispersal modelling in the Great Barrier Reef - Douchan Hanuise; Chieh Lin; Samantha Tol; Severine Choukroun; Michael A. Rasheed; Thomas Dobbelaere; Paul H. York; Timothy M. Smith; Robert G. Coles; Emmanuel Hanert; Alana Grech (Marine Environmental Research, 2026)

Assessing the fidelity of clay-size lithium isotopes as chemical-weathering tracers in detrital sedimentary successions - Xia Zhang; Chunming Lin; Robert W. Dalrymple; Cheng Cao; Daidu Fan; Guyue Tan; Xin Li (Geochimica et Cosmochimica Acta, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

High-throughput fingerprinting of hydrolysable tannins in wine and oak wood using in-source fragmentation on QTOF and QQQ platforms - Yanxin Lin; Bruce S. Pan; Robert (Qiang) Sui; Ping Yu; Misha T. Kwasniewski (Food Chemistry, 2026)

Unusually tight bending of subducting pacific plate causes the extreme depth of challenger deep - Jiangyang Zhang; Robert J. Stern; Fan Zhang; Jian Lin; Hongfeng Yang (Earth and Planetary Science Letters, 2026)

Bipolar volcanic ice-core synchronization of the entire last glacial period - Anders Svensson; Guido Vettoretti; Jia-mei Lin; Giulia Sinnl; Dorthe Dahl-Jensen; Jørgen Peder Steffensen; Sune Olander Rasmussen; Bo Vinther; Christine Hvidberg; Helle Astrid Kjær; Vasileios Gkinis; Eliza Cook; et al. (Quaternary Science Reviews, 2026)

Calcite TLM as a new natural reference material for in situ U-Pb geochronology and its geological implications - Tianyi Li; Ranran Chen; Shitou Wu; Rolf L. Romer; Nick M.W. Roberts; Kerstin Drost; David Chew; Marcel Guillong; Qian Ma; Yahui Yue; Shuangjian Li; Bohang Xie; et al. (Chemical Geology, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Resistance of shallow soil carbon to both short-term isolated and recurrent droughts in two semi-arid grasslands - Taofeek O. Muraina; Niwu Te; Saheed O. Jimoh; Robert Griffin-Nolan; Lin Song; Jiaqi Chen; Yuan Shi; Ahmed A. Amisu; Tilak Chaudhary; Qiang Yu; Melinda D. Smith; Alan K. Knapp; et al. (Oecologia, 2026)

Extent of threats to marine fish from the online aquarium trade in the United States - Bing Lin; Yiwen Zeng; Bryan To; Robert J. Holmberg; Andrew L. Rhyne; Michael Tlusty; David S. Wilcove (Conservation Biology, 2026)
The global marine aquarium hobby is a multibillion‐dollar industry, largely driven by demand from the United States. Much of this trade occurs online. We web scraped 4 major US‐based e‐commerce platforms selling marine aquarium fish to determine the retail price and source (wild capture, aquaculture, or both) of 13 families of ray‐finned marine fish ( Actinopterygii ). We supplemented this with ecological and economic trait data from FishBase and the International Union for Conservation of Nature (IUCN). Across all platforms and 13 popular fish taxonomic families, we found 734 unique species for sale, 89.2% (655 species) of which were sourced exclusively from the wild. A total of 45 species were of conservation concern (20 threatened species and 25 additional species with decreasing population trends), 38 of which were sourced solely from the wild. Retail price was significantly correlated with source, body length, minimum occupied depth, and schooling behavior. A further 100 species for sale were not listed as being in the aquarium trade in FishBase or by the IUCN, indicating incomplete information on this fishery in 2 important databases. For 58 species (encompassing 71 variants) with both wild‐caught and captive‐bred individuals for sale, aquaculture fish were a mean 28.1% (95% confidence interval 15.3) cheaper than their wild‐caught counterparts.

Robust deep reinforcement learning for improved energy-comfort performance in HVAC systems - Limao Zhang; Jing Guo; Chao Chen; Penghui Lin; Robert L.K. Tiong (Building and Environment, 2026)

The use of the serum progesterone strip test as a clinical tool for assessing reproductive status in replacement gilts - Preechaphon Taechamaeteekul; Umaporn Pimpitak; Junpen Suwimonteerabutr; Wanwisa Poonlapdecha; Nutthiwut Khun-arwut; Kittinan Komolpis; Sirirat Rengpipat; Kridtasak Sang-Gassanee; Hongyao Lin; Miquel Collell; Robert V. Knox; Padet Tummaruk (Theriogenology, 2025)

Walruses are potentially exposed to paralytic shellfish toxin concentrations that impact their health during Alexandrium blooms in the Alaskan Arctic - Patrick Charapata; Evangeline Fachon; Donald M. Anderson; Gay Sheffield; Emily K. Bowers; Robert S. Pickart; Peigen Lin; Kathi A. Lefebvre (Harmful Algae, 2025)

In vitro formation and growth of glycogen: experimental verification of theoretical predictions - Xin Liu; Ziyi Wang; Xin Lin; Wang Xu; Robert G. Gilbert (Carbohydrate Polymers, 2025)

Water savings policy in western Kansas: a decade-long satellite-based examination - Ramesh Dhungel; Robert Aiken; Xiaomao Lin; Shannon Kenyon; Paul D. Colaizzi; Dan O’Brien; R. Louis Baumhardt; Seth Kutikoff (Irrigation Science, 2025)

Putting Regional Fisheries Management Organisations' Climate Change House in Order - Kamal Azmi; Graham Pilling; Johann Bell; Yi‐Jay Chang; Adele Dutilloy; Timothy H. Frawley; Paul Hamer; John Hampton; Quentin Hanich; Tyla Hill‐Moana; Jhen Hsu; Glenn Hurry; et al. (Fish and Fisheries, 2025)
Climate change is expected to have significant impacts on the biology, abundance and distribution of transboundary fish stocks, not only among neighbouring countries within the jurisdictions of regional fisheries management organisations (RFMOs) but also between adjacent RFMOs. Using South Pacific albacore tuna ( Thunnus alalunga ) as a case study, we highlight how RFMOs need to understand the impacts of climate change on transboundary stocks under their purview with greater certainty. We identify four areas of research that should assist RFMOs to adapt their scientific processes—strengthened understanding of changes in the biology of target stocks; enhanced collection of data to support modelling; improved modelling of catch‐per‐unit of effort (CPUE) to better reflect climate change impacts on stock abundance for assessments; and ensuring that scientific advice is adaptive and robust to climate change, including through implementation of tested harvest strategies. Investments in these research areas should enable RFMOs to improve the science underpinning management measures designed to sustain transboundary stocks and increase fishery performance during climate change.

Sex specific gut bacterial community structure: implications for frailty risk in people with HIV - Aline Zaparte; John W. Lammons; Christopher M. Taylor; Meng Luo; Hui-Yi Lin; Robert W. Siggins; Patricia E. Molina; David A. Welsh (GeroScience, 2025)

Supplementation of boar semen extender with 5 μg of buserelin improves litter size and birth weight in gilts raised under tropical field conditions - Preechaphon Taechamaeteekul; Yosua Kristian Adi; Junpen Suwimonteerabutr; Kridtasak Sang-Gassanee; Hongyao Lin; Miquel Collell; Robert V. Knox; Padet Tummaruk (Theriogenology, 2025)

Saxitoxin Linked to Deaths of Northern Fur Seals in the Southeast Bering Sea - Kathi A. Lefebvre; Chelsea M. Campbell; Lauren M. Divine; Paul Melovidov; Hanna Hellen; Kathy Burek Huntington; Emily K. Bowers; Natalie Rouse; Evangeline Fachon; Thomas J. Farrugia; Robert S. Pickart; Peigen Lin; et al. (Marine Mammal Science, 2025)
In August 2024, a northern fur seal mortality event was observed on St. Paul Island, AK in the southeast (SE) Bering Sea. Ten seals in good body condition were found dead along with large accumulations of dead fish on Benson Beach located on St. Paul Island. Full necropsies of the five available adult seals, one pup, and several fish did not reveal any overt causes of death. Testing of tissues for the algal neurotoxins domoic acid (DA) and saxitoxin (STX) confirmed the presence of STX in multiple tissues and physiological exposure in all five adult NFS and the two fish available for testing. DA was not detected in any samples. Complimentary samples of the SE Bering Sea ecosystem during the same time frame and location as the die off revealed bloom densities of Alexandrium catenella (the dinoflagellate that produces STX), large A. catenella cyst beds, and high prevalences of STX in fish (100%, n = 22), zooplankton (93%, n = 28), clams (100%, n = 10) and worms (93% n = 15) in the foraging area of NFS. High STX concentrations were observed in fish, clams, worms, and NFS urine, providing compelling evidence for a STX poisoning event.

Nicotinamide riboside combined with exercise to treat hypertension in middle-aged and older adults: a pilot randomized clinical trial - Yi Lin; Rola S. Zeidan; Stephanie Lapierre-Nguyen; Hannah M. Costello; Stephen D. Anton; Thomas W. Buford; Demetra D. Christou; Michelle L. Gumz; Christiaan Leeuwenburgh; Christopher R. Martens; Mary M. McDermott; Marie E. Migaud; et al. (GeroScience, 2025)
Aerobic exercise lowers blood pressure (BP) with varying effects in hypertensive adults, potentially due to age-related nicotinamide adenine dinucleotide (NAD) metabolism dysregulation. This pilot randomized clinical trial (RCT) tested the efficacy of combining aerobic exercise with the NAD booster nicotinamide riboside (NR) to enhance BP control. In this double-blinded RCT, 54 sedentary adults (≥ 55 years) with mean daytime systolic BP (SBP) ≥ 130 mmHg were randomized to 6 weeks of 1000 mg/day of NR combined with 3 days/week of supervised 30-min walking exercise (NR + Ex), Placebo combined with the same exercise regimen (PL + Ex), or NR alone (NR). The primary outcome was daytime SBP. Other outcomes included pulse wave velocity (PWV), NAD catabolites, and nighttime BP. The primary comparison was between NR + Ex and PL + Ex. Of 54 participants (mean age 67 years, 61% female), 49 (NR + Ex: n = 15, PL + Ex: n = 16, NR: n = 18) completed all study visits (93% adherence to exercise and 90% to supplementation). NR + Ex (mean change = 5.19 ± 13.2 mmHg) did not reduce SBP more than PL + Ex (− 2.71 ± 10.5 mmHg). NR + Ex (− 0.31 ± 0.77 m/s) showed a trend toward a greater reduction in PWV. Levels of NAD catabolites were higher in NR groups. In a post hoc analysis, NR + Ex showed a trend toward greater nighttime BP reductions (systolic: − 9.6 ± 9.22; diastolic: − 4.51 ± 7.12 mmHg) in participants without antihypertensive medications. NR + Ex was not superior to PL + Ex in reducing BP in hypertensive middle-aged and older. However, trends toward greater nighttime BP reduction in NR + Ex in participants without antihypertensive medication warrant further investigation in a Phase IIb RCT. Graphical Abstract

Direct dating of Qaidam Basin stratigraphy, Northern Tibet - Deng Zeng; Lin Ding; Robert A. Spicer; Chao Wang; Chen Wu; Xiaodong Wang; Mike Widdowson; Jing Xie; Yahui Yue; Chenyuan Zhao; Xudong Guo (Earth and Planetary Science Letters, 2025)

Upper-layer circulation at the mouth of Amundsen Gulf, Arctic Ocean - Peigen Lin; Robert S. Pickart; Maria Pisareva; Bill Williams (Progress in Oceanography, 2025)

International Consortium on Ageing-Related Pathologies (ICCARP) Audiovestibular Group: fostering international consensus to refine International Classification of Diseases (ICD-11) codes for hearing loss across the life course - Dialechti Tsimpida; Michael A. Akeroyd; Barry L. Bentley; Shuvarthi Bhattacharjee; Michael R. Bowl; Emma Broome; Stuart R. G. Calimport; Sian Calvert; Gary Christopher; Tom Dening; Silvia Di Bonaventura; Ankita Goswami; et al. (GeroScience, 2025)

Linking sleep microstructure, blood markers of inflammation and metabolism, and cognition: mediation analysis in the osteoporotic fractures in men study - Claire Suen; Julia Ma; Xihong Lin; Robert J. Thomas; M. Brandon Westover; Katie Stone; Kristine Yaffe; Kristine E. Ensrud; Susan Redline; Rudolph E. Tanzi; Haoqi Sun; Can Zhang (GeroScience, 2025)

Biosolids-derived phosphorus persists in Florida sandy soils - JoAnn B. Donald; Robert G. Hatfield; Rex Ellis; Todd Z. Osborne; Allan R. Bacon; Yang Lin (Geoderma Regional, 2025)

Genomic and metabolic characterisation of a novel species Magnetominusculus dajiuhuensis DJH-1Ts sp. nov. from an acidic peatland - Pranami Goswami; Runjia Ji; Jianxun Shen; Andrew P. Roberts; Wei Lin (Systematic and Applied Microbiology, 2025)

International research initiative on genomics-guided sugarcane breeding - Xingtan Zhang; Jungang Wang; Noor-ul-Áin; Youxiong Que; Jisen Zhang; Javeria Abid; Peifang Zhao; Yuebin Zhang; Jishan Lin; Li-yu Chen; Yixue Bao; Robert Henry; et al. (Molecular Plant, 2025)

Nanoengineered cellulose for sustainable selective separation of precious metals from electronic waste - Roya Koshani; Shang-Lin Yeh; Mica L. Pitcher; Lucas Lawrence Franz; Mitchell Robert Davis; Min Ju Park; Said Khalifa Ahmed Al Qassabi; Joelson Patricio Manuel Alves; Younes Shekarian; Hevapathiranage Chandima Sudantha Subasinghe; Sarma V. Pisupati; Mohammad Rezaee; et al. (Chemical Engineering Journal, 2025)

A state-of-the-art empirical round robin validation of heat, air and moisture (HAM) models - Xinyuan Dang; Ana Sofia Guimarães; Andreas Sarkany; Anssi Laukkarinen; Bingyu Xu; Bruno Vanderschelden; Carsten Rode; Changchang Xia; Chi Feng; Chris Whitman; Daan Deckers; Hanyu Yang; et al. (Building and Environment, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Extreme Drought Increases the Temporal Variability of Grassland Productivity by Suppressing Dominant Grasses - Wentao Luo; Naohiro I. Ishii; Taofeek O. Muraina; Lin Song; Niwu Te; Robert J. Griffin‐Nolan; Ingrid J. Slette; Samuel R. P. J. Ross; Takehiro Sasaki; Jennifer A. Rudgers; Melinda D. Smith; Alan K. Knapp; et al. (Ecology Letters, 2025)
Extreme droughts are intensifying, yet their impact on temporal variability of grassland functioning and its drivers remains poorly understood. We imposed a 6‐year extreme drought in two semiarid grasslands to explore how drought influences the temporal variability of ANPP and identify potential stabilising mechanisms. Drought decreased ANPP while increasing its temporal variability across grasslands. In the absence of drought, ANPP variability was strongly driven by the dominant plant species (i.e., mass‐ratio effects), as captured by community‐weighted traits and species stability. However, drought decreased the dominance of perennial grasses, providing opportunities for subordinate species to alter the stability of productivity through compensatory dynamics. Specifically, under drought, species asynchrony emerged as a more important correlate of ANPP variability than community‐weighted traits or species stability. Our findings suggest that in grasslands, prolonged, extreme droughts may decrease the relative contribution of mass‐ratio effects versus compensatory dynamics to productivity stability by reducing the influence of dominant species.

The Combined Effects of Cadmium and Microplastic Mixtures on the Digestion, Energy Metabolism, Oxidative Stress Regulation, Immune Function, and Metabolomes in the Pearl Oyster (Pinctada fucata martensii) - Jiaying Yao; Zixin Gao; Zhixiang Wang; Zhanbo Ge; Yujing Lin; Luomin Huang; Jiaen Liu; Heqi Zou; Chuangye Yang; Robert Mkuye; Yuewen Deng (Fishes, 2025)
The accumulation of cadmium (Cd) and microplastics (MPs) can have major deleterious effects on the health of marine ecosystems and organisms, including the pearl oyster Pinctada fucata martensii. Here, we characterized the effects of Cd and MPs on key biochemical parameters of P. f. martensii via an experiment with various treatments. Pearl oysters were exposed to either only Cd (5 or 50 μg/L), only MPs (5 mg/L), or both Cd and MPs for 2 d, and this was followed by a 5-day recovery period. Measurements of the activities of lipase, amylase, protease, T-ATPase, catalase, glutathione peroxidase, acid phosphatase, and alkaline phosphatase enzymes, as well as the malondialdehyde content in the hepatopancreas, were made at various time points during the experiment. Metabolomics analysis of the gills was also performed. Significant interactions between time and treatment on lipase, protease, and catalase activities were observed. However, no significant effect of time–treatment interactions on amylase and T-ATPase activities was observed. Enzyme activities varied among groups both during the exposure period (6 to 48 h) and the recovery period. The malondialdehyde content was also increased throughout the experiment. Pathway analysis indicated that the purine metabolism, glycerophospholipid metabolism, nucleotide metabolism, arachidonic acid metabolism, neuroactive ligand–receptor interaction, and linoleic acid metabolism pathways were the most commonly affected under different treatments. The findings of our study revealed the differential effects of exposure time and treatment on enzyme activities and metabolites and their respective pathways. Our findings enhance our understanding of the biochemical responses of the pearl oyster P. f. martensii to environmental stressors, particularly Cd and MPs.

Strong thermospheric response to the almost undetectable substorm on May 29, 2023 - Yongliang Zhang; Qian Wu; Wenbin Wang; Larry Paxton; Robert Schaefer; Dong Lin; Lying Qian; Haonan Wu; Kun Wu; Ying Zou; Martin Connors (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Interactive effects of air pollutants and viral exposure on daily influenza hospital visits in Mongolia - Yihui Ge; Yan Lin; Oyu Tsogtbayar; Ser-Od Khuyagaa; Eelin Khurelbaatar; Jargalsaikhan Galsuren; Lauren Prox; Shiyu Zhang; Robert M. Tighe; Gregory C. Gray; Junfeng Zhang; Daramragchaa Ulziimaa; et al. (Environmental Research, 2025)

International research initiative on genomics-guided sugarcane breeding - Xingtan Zhang; Jungang Wang; Noor-ul-Áin; Youxiong Que; Jisen Zhang; Javeria Abid; Peifang Zhao; Yuebin Zhang; Jishan Lin; Li-yu Chen; Yixue Bao; Robert Herry; et al. (Molecular Plant, 2025)

Grassland bud and shoot demographic responses to single and recurrent droughts vary across an aridity gradient - Niwu Te; Robert J. Griffin‐Nolan; Ingrid J. Slette; Yuan Shi; Lin Song; Jiaqi Chen; Hongqiang Wang; Jianqiang Qian; Qiang Yu; Zhengwen Wang; Xiaotao Lü; Xingguo Han; et al. (Ecology, 2025)
Clonal demographic traits play important roles in regulating community dynamics. Yet, it remains unclear how the responses of these clonal traits to drought might depend on previous drought exposure, and how drought responses vary among grasslands. We conducted a repeated drought experiment across four grasslands along an aridity gradient in northern China. We assessed the effects of single (precipitation reduction in 2021–2022) versus recurrent (precipitation reduction in 2015–2018 and 2021–2022) drought on bud density, shoot density, and the ratio of bud to shoot density. Drought reduced bud density at all grasslands and shoot density at most grasslands. Drought reduced the ratio of bud‐to‐shoot density only in the most arid grasslands. Recurrent drought had larger negative effects than a single drought on bud density and composition of bud and shoot at only one of four grasslands, and on shoot density at two of four grasslands. Our results suggest that previous drought exposure can alter the response of plant clonal demographic traits to subsequent drought in some but not all grasslands, and that responses can vary with mean climate.

Epigenetic modifications control CYP1A1 Inducibility in human and rat keratinocytes - Lo-Wei Lin; Allison K. Ehrlich; Robert H. Rice (Toxicology and Applied Pharmacology, 2025)

Finite volume method: a good match to airborne gravimetry? - Xiaopeng Li; Robert Čunderlík; Marek Macák; Dana J. Caccamise; Zuzana Minarechová; Pavol Zahorec; Juraj Papčo; Daniel R. Roman; Jordan Krcmaric; Miao Lin (Journal of Geodesy, 2025)

Observations on Deraniyagala's beaked whale ( Mesoplodon hotaula ) in the South China Sea based on the first confirmed live sightings - Mingming Liu; Wenzhi Lin; Binshuai Liu; Shenglan Chen; Mingli Lin; Lijun Dong; Hui Kang; Mingyue Ouyang; Zixin Yang; Xiaoyu Huang; Massimiliano Rosso; L. Todd Pusser; et al. (Marine Mammal Science, 2025)
Deraniyagala's beaked whale, Mesoplodon hotaula , was previously known from eight published strandings and no confirmed live sightings, making it one of the least‐known cetaceans. We conducted six cetacean survey cruises in the South China Sea between 2019 and 2023, and during 120 sea‐days we recorded 12 sightings of unidentified Mesoplodon . From biopsy samples and acoustic recordings, five sightings were subsequently confirmed as M. hotaula. Using photographs, we provide the first field descriptions and observations of this species. The calf/juvenile has a distinctive facial coloration and dorsal striping pattern that appear to be diagnostic among Indo‐Pacific Mesoplodon ; among adult males, the dark rostrum of M. hotaula and the distinctively white‐tipped beak of ginkgo‐toothed beaked whale, M. ginkgodens , distinguish these similar‐looking, partially sympatric species. Mean group size was small (3.0, n = 5), with a preference for deep (2,156 m, n = 5), warm (30.3°C, n = 3) water. We update the known distribution of this species, present evidence of fishery interactions, and document the first reported mixed‐species Mesoplodon group: a juvenile Blainville's beaked whale M. densirostris associated with four M. hotaula. These sightings identify the South China Sea as a potentially important area for this almost completely unknown species.

Imperiled wanderlust lichens in steppe habitats of western North America comprise geographically structured mycobiont lineages and a reversal to sexual reproduction within this asexual clade - Robert Hadfield; Teagan Mulford; Makani L. Fisher; Abigail Borgmeier; Diego A. Ardon; Andrew D. Suchomel; Judicaël Fomekong-Lontchi; Laura Sutherland; Madison Huie; Pungki Lupiyaningdyah; Sierra Nichols; Ying Fei Lin; et al. (Molecular Phylogenetics and Evolution, 2024)

Outdoor physical activity is not associated with better mental health in a sample of predominantly Black people, but spending time in parks is - Amber L. Pearson; Wei Liu; Zihan Lin; Teresa H. Horton; Jennifer D. Roberts; Tim Chambers; Ashton Shortridge; Karin A. Pfeiffer; Joseph Gardiner (Urban Forestry & Urban Greening, 2024)

Effect of moisture (2 mol%) on CO2 enhanced desorption from nano-dispersed Na2O/Al2O3 for direct air capture - Soosan Kim; Xiao Lin; Robert J. Farrauto (Chemical Engineering Journal, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Prenatal blood metals, per- and polyfluoroalkyl substances and antigen- or mitogen-stimulated cord blood lymphocyte proliferation and cytokine secretion - Anna R. Smith; Pi-I.D. Lin; Sheryl L. Rifas-Shiman; Abby F. Fleisch; Robert O. Wright; Brent Coull; Patricia W. Finn; Emily Oken; Diane R. Gold; Andres Cardenas (Environmental Research, 2024)

Deciphering spatial-temporal dynamics of flood exposure in the United States, - Joynal Abedin; Lei Zou; Mingzheng Yang; Robert Rohli; Debayan Mandal; Yi Qiang; Humaira Akter; Bing Zhou; Binbin Lin; Heng Cai (Sustainable Cities and Society, 2024)

Challenges in assessing and managing multi-hazard risks: A European stakeholders perspective - Robert Šakić Trogrlić; Karina Reiter; Roxana L. Ciurean; Stefania Gottardo; Silvia Torresan; Anne Sophie Daloz; Lin Ma; Noemi Padrón Fumero; Sharon Tatman; Stefan Hochrainer-Stigler; Marleen C. de Ruiter; Julius Schlumberger; et al. (Environmental Science & Policy, 2024)

Where the rubber meets the road: Emerging environmental impacts of tire wear particles and their chemical cocktails - Paul M. Mayer; Kelly D. Moran; Ezra L. Miller; Susanne M. Brander; Stacey Harper; Manuel Garcia-Jaramillo; Victor Carrasco-Navarro; Kay T. Ho; Robert M. Burgess; Leah M. Thornton Hampton; Elise F. Granek; Margaret McCauley; et al. (Science of The Total Environment, 2024)

Observation of an acoustic topological Euler insulator with meronic waves - Bin Jiang; Adrien Bouhon; Shi-Qiao Wu; Ze-Lin Kong; Zhi-Kang Lin; Robert-Jan Slager; Jian-Hua Jiang (Science Bulletin, 2024)

Climate-regulation of organic carbon export in erosive mountain settings: A case study from Taiwan since the last glacial maximum - Li-Wei Zheng; Robert G. Hilton; Yuan-Pin Chang; Rick J. Yang; Xiaodong Ding; Xufeng Zheng; Tsung-Yu Lee; Hsi-Jih Lu; Jung-Tai Lu; Yu-Shih Lin; James T. Liu; Shuh-Ji Kao (Quaternary Science Reviews, 2024)

Non-targeted analysis and toxicity prediction for evaluation of photocatalytic membrane distillation removing organic contaminants from hypersaline oil and gas field-produced water - Himali M.K. Delanka-Pedige; Robert B. Young; Maha T. Abutokaikah; Lin Chen; Huiyao Wang; Kanchana A.B.I. Imihamillage; Sean Thimons; Michael A. Jahne; Antony J. Williams; Yanyan Zhang; Pei Xu (Journal of Hazardous Materials, 2024)

Dislocation-mediated interfacial re-equilibration of pyrite: An alternative model to interface-coupled dissolution-reprecipitation and gold remobilisation - Denis Fougerouse; Steven M. Reddy; Sumail; Joël Brugger; Nicolas Thébaud; William D.A. Rickard; Lin Yang; Zakaria Quadir; Malcolm P. Roberts; Andrew G. Tomkins; Laure Martin; Laura Petrella; et al. (Geochimica et Cosmochimica Acta, 2024)

Effects of titanium dioxide nanoparticle exposure on the gut microbiota of pearl oyster (Pinctada fucata martensii) - Fengfeng Li; Yujing Lin; Chuangye Yang; Yilong Yan; Ruijuan Hao; Robert Mkuye; Yuewen Deng (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Determinants of microbiome composition: Insights from free‐ranging hybrid zebras ( Equus quagga × grevyi ) - Joel O. Abraham; Bing Lin; Audrey E. Miller; Lucas P. Henry; Margaret Y. Demmel; Rosemary Warungu; Margaret Mwangi; Patrick M. Lobura; Luisa F. Pallares; Julien F. Ayroles; Robert M. Pringle; Daniel I. Rubenstein (Molecular Ecology, 2024)
The composition of mammalian gut microbiomes is highly conserved within species, yet the mechanisms by which microbiome composition is transmitted and maintained within lineages of wild animals remain unclear. Mutually compatible hypotheses exist, including that microbiome fidelity results from inherited dietary habits, shared environmental exposure, morphophysiological filtering and/or maternal effects. Interspecific hybrids are a promising system in which to interrogate the determinants of microbiome composition because hybrids can decouple traits and processes that are otherwise co‐inherited in their parent species. We used a population of free‐living hybrid zebras ( Equus quagga × grevyi ) in Kenya to evaluate the roles of these four mechanisms in regulating microbiome composition. We analysed faecal DNA for both the trn L‐P6 and the 16S rRNA V4 region to characterize the diets and microbiomes of the hybrid zebra and of their parent species, plains zebra ( E. quagga ) and Grevy's zebra ( E. grevyi ). We found that both diet and microbiome composition clustered by species, and that hybrid diets and microbiomes were largely nested within those of the maternal species, plains zebra. Hybrid microbiomes were less variable than those of either parent species where they co‐occurred. Diet and microbiome composition were strongly correlated, although the strength of this correlation varied between species. These patterns are most consistent with the maternal‐effects hypothesis, somewhat consistent with the diet hypothesis, and largely inconsistent with the environmental‐sourcing and morphophysiological‐filtering hypotheses. Maternal transmittance likely operates in conjunction with inherited feeding habits to conserve microbiome composition within species.

On the brink of explosion? Identifying the source and potential spread of introduced Zosterops white-eyes in North America - Devon A. DeRaad; Marlon E. Cobos; Natalie R. Hofmeister; Lucas H. DeCicco; Madhvi X. Venkatraman; Isao Nishiumi; Bailey McKay; Fa-Sheng Zou; Kazuto Kawakami; Chang-Hoe Kim; Ruey-Shing Lin; Cheng-Te Yao; et al. (Biological Invasions, 2024)

Cross-sectional and prospective associations of early childhood circulating metals with early and mid-childhood cognition in the Project Viva cohort - Ruwan Thilakaratne; Pi-I D. Lin; Sheryl L. Rifas-Shiman; Julio Landero; Robert O. Wright; David Bellinger; Emily Oken; Andres Cardenas (Environmental Research, 2024)

Variability in the phytoplankton response to upwelling across an iron limitation mosaic within the California current system - YuanYu Lin; Olivia Torano; Logan Whitehouse; Emily Pierce; Claire P. Till; Matthew Hurst; Robert Freiberger; Travis Mellett; Maria T. Maldonado; Jian Guo; Mariam Sutton; David Zeitz; et al. (Limnology and Oceanography, 2024)
Coastal upwelling currents such as the California Current System (CCS) comprise some of the most productive biological systems on the planet. Diatoms dominate these upwelling events in part due to their rapid response to nutrient entrainment. In this region, they may also be limited by the micronutrient iron (Fe), an important trace element primarily involved in photosynthesis and nitrogen assimilation. The mechanisms behind how diatoms physiologically acclimate to the different stages of the upwelling conveyor belt cycle remain largely uncharacterized. Here, we explore their physiological and metatranscriptomic response to the upwelling cycle with respect to the Fe limitation mosaic that exists in the CCS. Subsurface, natural plankton assemblages that would potentially seed surface blooms were examined over wide and narrow shelf regions. The initial biomass and physiological state of the phytoplankton community had a large impact on the overall response to simulated upwelling. Following on‐deck incubations under varying Fe physiological states, our results suggest that diatoms quickly dominated the blooms by “frontloading” nitrogen assimilation genes prior to upwelling. However, diatoms subjected to induced Fe limitation exhibited reductions in carbon and nitrogen uptake and decreasing biomass accumulation. Simultaneously, they exhibited a distinct gene expression response which included increased expression of Fe‐starvation induced proteins and decreased expression of nitrogen assimilation and photosynthesis genes. These findings may have significant implications for upwelling events in future oceans, where changes in ocean conditions are projected to amplify the gradient of Fe limitation in coastal upwelling regions.

Determination of soil water retention curves from thermal conductivity curves, texture, bulk density, and field capacity - Lin Liu; Yili Lu; Robert Horton; Tusheng Ren (Soil and Tillage Research, 2024)

A Potential Source of Bias in Group-Level EEG Microstate Analysis - Michael Murphy; Jun Wang; Chenguang Jiang; Lei A. Wang; Nataliia Kozhemiako; Yining Wang; Jun Wang; Chenguang Jiang; Guanchen Gai; Kai Zou; Zhe Wang; Xiaoman Yu; et al. (Brain Topography, 2024)

Grassland sensitivity to drought is related to functional composition across E ast A sia and N orth A merica - Lin Song; Robert J. Griffin‐Nolan; Taofeek O. Muraina; Jiaqi Chen; Niwu Te; Yuan Shi; Kenneth D. Whitney; Bingchuan Zhang; Qiang Yu; Melinda D. Smith; Xiaoan Zuo; Zhengwen Wang; et al. (Ecology, 2024)
Plant traits can be helpful for understanding grassland ecosystem responses to climate extremes, such as severe drought. However, intercontinental comparisons of how drought affects plant functional traits and ecosystem functioning are rare. The Extreme Drought in Grasslands experiment (EDGE) was established across the major grassland types in East Asia and North America (six sites on each continent) to measure variability in grassland ecosystem sensitivity to extreme, prolonged drought. At all sites, we quantified community‐weighted mean functional composition and functional diversity of two leaf economic traits, specific leaf area and leaf nitrogen content, in response to drought. We found that experimental drought significantly increased community‐weighted means of specific leaf area and leaf nitrogen content at all North American sites and at the wetter East Asian sites, but drought decreased community‐weighted means of these traits at moderate to dry East Asian sites. Drought significantly decreased functional richness but increased functional evenness and dispersion at most East Asian and North American sites. Ecosystem drought sensitivity (percentage reduction in aboveground net primary productivity) positively correlated with community‐weighted means of specific leaf area and leaf nitrogen content and negatively correlated with functional diversity (i.e., richness) on an intercontinental scale, but results differed within regions. These findings highlight both broad generalities but also unique responses to drought of community‐weighted trait means as well as their functional diversity across grassland ecosystems.

Efficacy and Safety of a Novel Formulation Liquid Botulinum Toxin, RelabotulinumtoxinA, When used for Combination Treatment of Glabellar and Lateral Canthal Lines - Vince Bertucci; Joel Schlessinger; John Joseph; Ava Shamban; Z. Paul Lorenc; Robert Weiss; Leslie Baumann; Mark S. Nestor; Heidi B. Prather; Derek Jones; Alexander S. Donath; Rebecca Kazin; et al. (Toxicon, 2024)

Aging studies of Dual functional materials for CO2 direct air capture with in situ methanation under simulated ambient conditions: Ru thrifting for cost reduction - Yuanchunyu (Iris) Lin; Monica J. Abdallah; Jonathan E. Peters; Tianyi Luo; Huan Sheng; Yee Lee Chen; Robert J. Farrauto (Chemical Engineering Journal, 2024)

CAPA-IVM improves the cytoplasmic quality of in vitro-matured oocytes from unstimulated mice - Xueqi Gong; Lin Shen; Hanwang Zhang; Jihui Ai; Robert B. Gilchrist; Yiqing Zhao (Theriogenology, 2023)

Radiometric assessment of OLCI, VIIRS, and MODIS using fiducial reference measurements along the Atlantic Meridional Transect - Silvia Pardo; Gavin H. Tilstone; Robert J.W. Brewin; Giorgio Dall'Olmo; Junfang Lin; Francesco Nencioli; Hayley Evers-King; Tânia G.D. Casal; Craig J. Donlon (Remote Sensing of Environment, 2023)

The Pacific water flow branches in the eastern Chukchi Sea - Robert S. Pickart; Peigen Lin; Frank Bahr; Leah T. McRaven; Jie Huang; Astrid Pacini; Kevin R. Arrigo; Carin J. Ashjian; Catherine Berchok; Mark F. Baumgartner; Kyoung-Ho Cho; Lee W. Cooper; et al. (Progress in Oceanography, 2023)

The late Eocene rise of SE Tibet formed an Asian ‘Mediterranean’ climate - Chenyuan Zhao; Zhongyu Xiong; Alex Farnsworth; Robert A. Spicer; Songlin He; Chao Wang; Deng Zeng; Fulong Cai; Houqi Wang; Xiaolong Tian; Paul J. Valdes; Ciren Lamu; et al. (Global and Planetary Change, 2023)

Nepalese indoor cookstove smoke extracts alter human airway epithelial gene expression, DNA methylation and hydroxymethylation - Poojitha Rajasekar; Robert J. Hall; K.C. Binaya; Parth S. Mahapatra; Siva P. Puppala; Dhruma Thakker; Julia L. MacIsaac; David Lin; Michael Kobor; Charlotte E. Bolton; Ian Sayers; Ian P. Hall; et al. (Environmental Pollution, 2023)

Field reconnaissance and observations from the February 6, 2023, Turkey earthquake sequence - Gulen Ozkula; Robert K. Dowell; Tugce Baser; Jui-Liang Lin; Ozgun A. Numanoglu; Okan Ilhan; C. Guney Olgun; Cheng-Wei Huang; Tunc Deniz Uludag (Natural Hazards, 2023)

Estimating soil water retention curves from thermal conductivity measurements: A percolation-based effective-medium approximation - Yongwei Fu; Lin Liu; Yili Lu; Robert Horton; Tusheng Ren; Joshua Heitman (Journal of Hydrology, 2023)

Formation and circulation of newly ventilated winter water in the western Beaufort Sea - Peigen Lin; Robert S. Pickart; Thomas J. Weingartner; Harper L. Simmons; Motoyo Itoh; Takashi Kikuchi (Progress in Oceanography, 2023)

Neutralizing Antibody Validation Testing and Reporting Harmonization - Heather Myler; João Pedras-Vasconcelos; Todd Lester; Francesca Civoli; Weifeng Xu; Bonnie Wu; Inna Vainshtein; Linlin Luo; Mohamed Hassanein; Susana Liu; Swarna Suba Ramaswamy; Johanna Mora; et al. (The AAPS Journal, 2023)
Evolving immunogenicity assay performance expectations and a lack of harmonized neutralizing antibody validation testing and reporting tools have resulted in significant time spent by health authorities and sponsors on resolving filing queries. A team of experts within the American Association of Pharmaceutical Scientists’ Therapeutic Product Immunogenicity Community across industry and the Food and Drug Administration addressed challenges unique to cell-based and non-cell-based neutralizing antibody assays. Harmonization of validation expectations and data reporting will facilitate filings to health authorities and are described in this manuscript. This team provides validation testing and reporting strategies and tools for the following assessments: (1) format selection; (2) cut point; (3) assay acceptance criteria; (4) control precision; (5) sensitivity including positive control selection and performance tracking; (6) negative control selection; (7) selectivity/specificity including matrix interference, hemolysis, lipemia, bilirubin, concomitant medications, and structurally similar analytes; (8) drug tolerance; (9) target tolerance; (10) sample stability; and (11) assay robustness. Graphical Abstract

Shifts in the composition of nitrogen deposition in the conterminous United States are discernable in stream chemistry - Meredith G. Lassiter; Jiajia Lin; Jana E. Compton; Jennifer Phelan; Robert D. Sabo; John L. Stoddard; Stephen R. McDow; Tara L. Greaver (Science of The Total Environment, 2023)

Bipolar ice-core records constrain possible dates and global radiative forcing following the ∼74 ka Toba eruption - Jiamei Lin; Peter M. Abbott; Michael Sigl; Jørgen P. Steffensen; Robert Mulvaney; Mirko Severi; Anders Svensson (Quaternary Science Reviews, 2023)

The IV International Symposium on Fungal Stress and the XIII International Fungal Biology Conference - Alene Alder-Rangel; Alexandre Melo Bailão; Alfredo Herrera-Estrella; Amanda E.A. Rangel; Attila Gácser; Audrey P. Gasch; Claudia B.L. Campos; Christina Peters; Francine Camelim; Fulvia Verde; Geoffrey Michael Gadd; Gerhard Braus; et al. (Fungal Biology, 2023)

Extraction, structure and bioactivities of polysaccharides from Sanghuangporus spp.: A review - Genglan Lin; Yanying Li; Xiaohua Chen; Fuming Zhang; Robert J. Linhardt; Anqiang Zhang (Food Bioscience, 2023)

Modeling microstructural mechanical behavior of expansive soil at various water contents and dry densities by molecular dynamics simulation - Jiapei Du; Annan Zhou; Xiaoshan Lin; Dilan Robert; Filippo Giustozzi; Jayantha Kodikara (Computers and Geotechnics, 2023)

Progerin induces a phenotypic switch in vascular smooth muscle cells and triggers replication stress and an aging-associated secretory signature - Nuria Coll-Bonfill; Urvashi Mahajan; Elena V. Shashkova; Chien-Jung Lin; Robert P. Mecham; Susana Gonzalo (GeroScience, 2023)

Evaluating historic and modern optical techniques for monitoring phytoplankton biomass in the Atlantic Ocean - Robert J. W. Brewin; Jaime Pitarch; Giorgio Dall’Olmo; Hendrik J. van der Woerd; Junfang Lin; Xuerong Sun; Gavin H. Tilstone (Frontiers in Marine Science, 2023)
Traditional measurements of the Secchi depth ( z SD ) and Forel-Ule colour were collected alongside modern radiometric measurements of ocean clarity and colour, and in-situ measurements of chlorophyll-a concentration (Chl-a), on four Atlantic Meridional Transect (AMT) cruises. These data were used to evaluate historic and modern optical techniques for monitoring Chl-a, and to evaluate remote-sensing algorithms. Historic and modern optical measurements were broadly consistent with current understanding, with Secchi depth inversely related to Forel-Ule colour and to beam and diffuse attenuation, positively related to the ratio of blue to green remote-sensing reflectance and euphotic depth. The relationship between Secchi depth and Forel-Ule on AMT was found to be in closer agreement to historical relationships when using data of the Forel-Ule colour of infinite depth, rather than the Forel-Ule colour of the water above the Secchi disk at half z SD . Over the range of 0.03-2.95 mg m -3 , Chl-a was tightly correlated with these optical variables, with the ratio of blue to green remote-sensing reflectance explaining the highest amount of variance in Chl-a (89%), closely followed by the Secchi depth (85%) and Forel-Ule colour (71-81%, depending on the scale used). Existing algorithms that predict Chl-a from these variables were evaluated, and found to perform well, albeit with some systematic differences. Remote sensing algorithms of Secchi depth were in good agreement with in-situ data over the range of values collected (8.5 - 51.8 m, r 2 >0.77, unbiased root mean square differences around 4.5 m), but with a slight positive bias (2.0 - 5.4 m). Remote sensing algorithms of Forel-Ule agreed well with Forel-Ule colour data of infinite water ( r 2 >0.68, mean differences <1). We investigated the impact of environmental conditions and found wind speed to impact the estimation of z SD , and propose a path forward to include the effect of wind in current Secchi depth theory. We discuss the benefits and challenges of collecting measurements of the Secchi depth and Forel-Ule colour and propose future directions for research. Our dataset is made publicly available to support the research community working on the topic.

Historical biomonitoring of pollution trends in the North Pacific using archived samples from the Continuous Plankton Recorder Survey - Kefeng Li; Jane C. Naviaux; Sai Sachin Lingampelly; Lin Wang; Jonathan M. Monk; Claire M. Taylor; Clare Ostle; Sonia Batten; Robert K. Naviaux (Science of The Total Environment, 2023)

Limits of oxygen isotope palaeoaltimetry in Tibet - Alex Farnsworth; Paul J. Valdes; Lin Ding; Robert A. Spicer; Shi-Hu Li; Tao Su; Shufeng Li; Caitlyn R. Witkowski; Zhongyu Xiong (Earth and Planetary Science Letters, 2023)

Experimental and kinetic model evaluation of HONO production from surface nitrate photolysis - Youfeng Wang; Jianshu Wang; Yaru Wang; Yingjie Zhang; Robert Woodward-Massey; Chong Zhang; Yu Kuang; Jiali Zhu; Jing Shang; Xin Li; Limin Zeng; Weili Lin; et al. (Atmospheric Environment, 2023)

In situ derived sulfated/sulfonated carbon nanogels with multi-protective effects against influenza a virus - Hung-Yun Lin; Ka-Long Luo; Ju-Yi Mao; Chin-Jung Lin; Chen-Yow Wang; Lauren Panny; Shiow-Yi Chen; Shih-Chao Lin; Chih-Ching Huang; Scott G. Harroun; Robert Y.L. Wang; Chang-Jer Wu (Chemical Engineering Journal, 2023)

Responses of a semiarid grassland to recurrent drought are linked to community functional composition - Wentao Luo; Taofeek O. Muraina; Robert J. Griffin‐Nolan; Wang Ma; Lin Song; Wei Fu; Qiang Yu; Alan K. Knapp; Zhengwen Wang; Xingguo Han; Scott L. Collins (Ecology, 2023)
Recurrent droughts are an inevitable consequence of climate change, yet how grasslands respond to such events is unclear. We conducted a 6‐year rainfall manipulation experiment in a semiarid grassland that consisted of an initial 2‐year drought (2015–2016), followed by a recovery period (2017–2018) and, finally, a second 2‐year drought (2019–2020). In each year, we estimated aboveground net primary productivity (ANPP), species richness, community‐weighted mean (CWM) plant traits, and several indices of functional diversity. The initial drought led to reduced ANPP, which was primarily driven by limited growth of forbs in the first year and grasses in the second year. Total ANPP completely recovered as the rapid recovery of grass productivity compensated for the slow recovery of forb productivity. The subsequent drought led to a greater reduction in total ANPP than the initial drought due to the greater decline of both grass and forb productivity. The structural equation models revealed that soil moisture influenced ANPP responses directly during the initial drought, and indirectly during the subsequent drought by lowering functional diversity, which resulted in reduced total ANPP. Additionally, ANPP was positively influenced by CWM plant height and leaf nitrogen during the recovery period and recurrent drought, respectively. Overall, the greater impact of the second drought on ecosystem function than the initial drought, as well as the underlying differential mechanism, underscores the need for an understanding of how increased drought frequency may alter semiarid grassland functioning.

Early pregnancy essential and non-essential metal mixtures and maternal antepartum and postpartum depressive symptoms - Lisa B. Rokoff; Andres Cardenas; Pi-I D. Lin; Sheryl L. Rifas-Shiman; Robert O. Wright; Michelle Bosquet Enlow; Brent A. Coull; Emily Oken; Susan A. Korrick (NeuroToxicology, 2023)

Coastal upwelling enhances abundance of a symbiotic diazotroph (UCYN-A) and its haptophyte host in the Arctic Ocean - Corday R. Selden; Sveinn V. Einarsson; Kate E. Lowry; Katherine E. Crider; Robert S. Pickart; Peigen Lin; Carin J. Ashjian; P. Dreux Chappell (Frontiers in Marine Science, 2022)
The apparently obligate symbiosis between the diazotroph Candidatus Atelocyanobacterium thalassa (UCYN-A) and its haptophyte host, Braarudosphaera bigelowii , has recently been found to fix dinitrogen (N 2 ) in polar waters at rates (per cell) comparable to those observed in the tropical/subtropical oligotrophic ocean basins. This study presents the novel observation that this symbiosis increased in abundance during a wind-driven upwelling event along the Alaskan Beaufort shelfbreak. As upwelling relaxed, the relative abundance of B. bigelowii among eukaryotic phytoplankton increased most significantly in waters over the upper slope. As the host’s nitrogen demands are believed to be supplied primarily by UCYN-A, this response suggests that upwelling may enhance N 2 fixation as displaced coastal waters are advected offshore, potentially extending the duration of upwelling-induced phytoplankton blooms. Given that such events are projected to increase in intensity and number with ocean warming, upwelling-driven N 2 fixation as a feedback on climate merits investigation.

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

Historical trend of probable maximum precipitation in Utah and associated weather types - Hongping Gu; S.‐Y. Simon Wang; Yen‐Heng Lin; Jonathan Meyer; Robert Gillies; Everett Taylor; Binod Pokharel (International Journal of Climatology, 2022)
This study assesses the impact global climate change has had on the theoretical upper limit of precipitation for Utah's watersheds by examining historical trends in probable maximum precipitation (PMP), a metric widely used for dam construction and management. Trends in the factors of PMP driven by both frontal and monsoonal storm scenarios were studied using two networks of surface weather stations and modern gridded datasets spanning 1981–2018. It was found that the historical trend in both 3‐hr and 24‐hr PMP estimations exhibited a statistically significant increasing trend, despite that the magnitude of the trend was sensitive to which dataset was examined and the data's spatial resolution. Over the 24‐hr time scale, an interesting deviation in PMP trends was found where frontal storm events demonstrated increasing PMP trends compared to decreasing PMP trends for monsoonal storm events. However, both storm types demonstrated increasing trends over shorter 3‐hr durations, suggesting a universal increase in convective storm intensity. PMP estimates also demonstrated a dependency on the type and resolution of meteorological data used, where higher‐resolution data generally produced greater PMP values and weaker trends. A discussion on the potential causes of these dependencies is provided. This study implies the need to take the historical PMP trend into account for future PMP estimates, especially when coarse‐resolution data are used for conventional PMP studies.

A Wet/Dry Point Treatment Method of FVCOM, Part I: Stability Experiments - Changsheng Chen; Jianhua Qi; Hedong Liu; Robert Beardsley; Huichan Lin; Geoffrey Cowles (Journal of Marine Science and Engineering, 2022)
A 3-dimensional wet/dry point treatment method was developed for the unstructured-grid Finite-Volume Community Ocean Model (FVCOM). Analytical equations were derived to examine discretized errors that occurred during the flooding/drying process by the wet/dry point treatment for the flooding/drying process. Numerical experiments were carried out for an idealized estuary, including the inter-tidal zone. The model results show that if the ratio of internal to external mode time steps (Isplit) is appropriately selected, FVCOM was capable of simulating the flooding/drying process with sufficient accuracy to ensure the mass conservation. The up-bound limit of Isplit was restricted by the bathymetric slope of the inter-tidal zone, external mode time step, horizontal/vertical resolution, and amplitude of tidal forcing at the open boundary, as well as the thickness of the viscous layer specified in the model. Criteria for time steps via these parameters were derived from these experiments, which provide a helpful guide in selecting Isplit for applying FVCOM to realistic geometric estuaries.

In Vitro Assessment of Transporter Mediated Perpetrator DDIs for Several Hepatitis C Virus Direct-Acting Antiviral Drugs and Prediction of DDIs with Statins Using Static Models - Xiaoyan Chu; Grace Hoyee Chan; Robert Houle; Meihong Lin; Jocelyn Yabut; Christine Fandozzi (The AAPS Journal, 2022)

Anatomy and white-matter connections of the precuneus - Onur Tanglay; Isabella M. Young; Nicholas B. Dadario; Robert G. Briggs; R. Dineth Fonseka; Vukshitha Dhanaraj; Jorge Hormovas; Yueh-Hsin Lin; Michael E. Sughrue (Brain Imaging and Behavior, 2022)

Legacy effects of a multi-year extreme drought on belowground bud banks in rhizomatous vs bunchgrass-dominated grasslands - Jianqiang Qian; Ziyue Guo; Taofeek O. Muraina; Niwu Te; Robert J. Griffin-Nolan; Lin Song; Chong Xu; Qiang Yu; Zhiming Zhang; Wentao Luo (Oecologia, 2022)

The difference in the intracellular Arg/Lys-rich and EHLVY motifs contributes to distinct subcellular distribution of HAI-1 versus HAI-2 - Nanxi Huang; Robert B. Barndt; Dajun D. Lu; Qiaochu Wang; Shih-Ming Huang; Jehng-Kang Wang; Ping-Ying Chang; Chao-Yang Chen; Je-Ming Hu; Hui-Chen Su; Michael D. Johnson; Chen-Yong Lin (Human Cell, 2022)

Harmful Algal Blooms in the Alaskan Arctic: An Emerging Threat as the Ocean Warms - Donald Anderson; Evangeline Fachon; Katherine Hubbard; Kathi Lefebvre; Peigen Lin; Robert Pickart; Mindy Richlen; Gay Sheffield; Caroline Van Hemert (Oceanography, 2022)
Harmful algal blooms (HABs) present an emerging threat to human and ecosystem health in the Alaskan Arctic. Two HAB toxins are of concern in the region: saxitoxins (STXs), a family of compounds produced by the dinoflagellate Alexandrium catenella, and domoic acid (DA), produced by multiple species in the diatom genus Pseudo-nitzschia. These potent neurotoxins cause paralytic and amnesic shellfish poisoning, respectively, in humans, and can accumulate in marine organisms through food web transfer, causing illness and mortality among a suite of wildlife species. With pronounced warming in the Arctic, along with enhanced transport of cells from southern waters, there is significant potential for more frequent and larger HABs of both types. STXs and DA have been detected in the tissues of a range of marine organisms in the region, many of which are important food resources for local residents. The unique nature of the Alaskan Arctic, including difficult logistical access, lack of response infrastructure, and reliance of coastal populations on the noncommercial acquisition of marine resources for nutritional, cultural, and economic well-being, poses urgent and significant challenges as this region warms and the potential for impacts from HABs expands.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Population, Reproductive and Fishery Dynamics of Spotted Box Crab (Calappa philargius), a New Claw-Only Fishery Species, in the Southern Taiwan Strait, China - Bai-an Lin; Yan Jiang; Robert Boenish; Qing Xu; Min Liu (Frontiers in Marine Science, 2021)
The spotted box crab Calappa philargius (Calappidae) is an increasingly consumed species in China, mainly sourced from a claw-only fishery. Being a not well-characterized species in the literature, this study is warranted to inform sustainable management approaches. Here we report on the first in-depth overview on biology and fishery dynamics of C. philargius in the southern Taiwan Strait of China. Whole body crabs ( N = 1,009) were collected monthly from January to December 2019 from trawlers, operating in the southern Taiwan Strait; sample collection was absent from May to July because of the national fishing moratorium regulation. Sex ratio, growth pattern, size at maturity and fecundity were estimated. The overall male: female ratio was 1: 1.47, significantly differing from the 1: 1 ( p < 0.01); monthly sex ratio variations were also significant ( p < 0.01), suggesting possible seasonal sexual segregation. We found the carapace widths (CW) of males were significantly larger than those of females ( p < 0.01). Based on the occurrence and percentages of berried females, we identified twin spawning events in January–April and August–October with the overall peak occurring in February. Size at 50% female maturity was 11.47 cm CW. Female absolute fecundity was significantly related to CW via a power function relationship ( N = 14, p < 0.01). The estimated average claw yield was 36.28 ± 3.07% of the whole body weight ( N = 95), irrespective of sex and size ( p > 0.5). Capture and trade data of C. philargius using trawl and trap fishing gears were documented to characterize claw-only fishery dynamics for future research and sustainable use.

Risk of two common glandular cell-type cancers (breast and colorectal cancers) in Chinese occupational chefs: a nationwide ecological study in Taiwan - Pei-Chen Lin; Chiung‑Yu Peng; Chih‑Hong Pan; Jui-Ying Lee; Tusty-Jiuan Hsieh; Yun-Shiuan Chuang; Robert J. Turesky; Chia-Fang Wu; Ming-Tsang Wu (International Archives of Occupational and Environmental Health, 2021)

Pomelo fruit wastes are potentially valuable antioxidants, anti-inflammatories, antihypertensives, and antihyperglycemics - Li-Yun Lin; Chi-Yun Huang; Kuan-Chou Chen; Robert Y. Peng (Horticulture, Environment, and Biotechnology, 2021)
Grapefruit (G) parts contain abundant phenolic acids and flavonoids (PPNs and FLVs). The wastes created from exocarps, mesocarps (G wastes, GW) and waste blanching water (WBW) lead to a considerable loss of PPNs and FLVs. Here, we assessed Buntan (CB), Buntan Hayata (CBH), and Peiyu (CP) cultivars and observed considerable amounts of PPNs and FLVs. The ethanolic extracts of GW (GWE) and WBW contained gallic acid, protocatechuic acid, chlorogenic acid, caffeic acid, ferulic acid, coumaric acid, naringin, hesperidin, diosmin, quercetin, hesperetin, nobiletin, and tangeretin (GWC). GWE has previously been reported to be a relatively active antioxidant, anti-inflammatory (based on the expression of TNF-α in Raw264.7 cells), antihypertensive, and anti-hyperglycemic compound. The IC 50 values for antihyperglycemic activity with WBW for α-amylase were as follows: CB (27.96 ± 0.03 mg/mL) < CP (28.13 ± 0.19 mg/mL) < CBH (41.60 ± 0.16 mg/mL), and those for α-glucosidase were CB (1.80 ± 0.03 mg/mL) < CP (2.97 ± 0.29 mg/mL) < CBH (9.10 ± 0.51 mg/mL). GWC upregulated Glut4 in HepG2 cells, as well as the insulin secretion capability, and intracellular levels in RIN-m5F cells, and it downregulated DPP4 in HepG2 cells. The IC 50 values for the angiotensin-converting enzyme activity were: CBP (5.10 ± 0.02 mg/mL) < CB (7.24 ± 0.65 mg/mL) < CP (8.60 ± 2.03 mg/mL). Our results indicate that PPNs and FLVs present in GW are worth reclaiming.

Targeted deletion of HAI-1 increases prostasin proteolysis but decreases matriptase proteolysis in human keratinocytes - Dajun D. Lu; Yayun Gu; Sheng-Wen A. Li; Robert J. Barndt; Shih-Ming Huang; Jehng-Kang Wang; Hui Chen Su; Michael D. Johnson; Chen-Yong Lin (Human Cell, 2021)

From zero to infinity: Minimum to maximum diversity of the planet by spatio‐parametric Rao’s quadratic entropy - Duccio Rocchini; Matteo Marcantonio; Daniele Da Re; Giovanni Bacaro; Enrico Feoli; Giles M. Foody; Reinhard Furrer; Ryan J. Harrigan; David Kleijn; Martina Iannacito; Jonathan Lenoir; Meixi Lin; et al. (Global Ecology and Biogeography, 2021)
Aim The majority of work done to gather information on the Earth's biodiversity has been carried out using in‐situ data, with known issues related to epistemology (e.g., species determination and taxonomy), spatial uncertainty, logistics (time and costs), among others. An alternative way to gather information about spatial ecosystem variability is the use of satellite remote sensing. It works as a powerful tool for attaining rapid and standardized information. Several metrics used to calculate remotely sensed diversity of ecosystems are based on Shannon’s information theory, namely on the differences in relative abundance of pixel reflectances in a certain area. Additional metrics like the Rao’s quadratic entropy allow the use of spectral distance beside abundance, but they are point descriptors of diversity, that is they can account only for a part of the whole diversity continuum. The aim of this paper is thus to generalize the Rao’s quadratic entropy by proposing its parameterization for the first time. Innovation The parametric Rao’s quadratic entropy, coded in R, (a) allows the representation of the whole continuum of potential diversity indices in one formula, and (b) starting from the Rao’s quadratic entropy, allows the explicit use of distances among pixel reflectance values, together with relative abundances. Main conclusions The proposed unifying measure is an integration between abundance‐ and distance‐based algorithms to map the continuum of diversity given a satellite image at any spatial scale. Being part of the rasterdiv R package, the proposed method is expected to ensure high robustness and reproducibility.

Glutathione and the intracellular labile heme pool - Rosemary O’Keeffe; Gladys Oluyemisi Latunde-Dada; Yu-Lin Chen; Xiaole L. Kong; Agostino Cilibrizzi; Robert C. Hider (BioMetals, 2021)
One candidate for the cytosolic labile iron pool is iron(II)glutathione. There is also a widely held opinion that an equivalent cytosolic labile heme pool exists and that this pool is important for the intracellular transfer of heme. Here we describe a study designed to characterise conjugates that form between heme and glutathione. In contrast to hydrated iron(II), heme reacts with glutathione, under aerobic conditions, to form the stable hematin–glutathione complex, which contains iron(III). Thus, glutathione is clearly not the cytosolic ligand for heme, indeed we demonstrate that the rate of heme degradation is enhanced in the presence of glutathione. We suggest that the concentration of heme in the cytosol is extremely low and that intracellular heme transfer occurs via intracellular membrane structures. Should any heme inadvertently escape into the cytosol, it would be rapidly conjugated to glutathione thereby protecting the cell from the toxic effects of heme.

The influence of vector‐borne disease on human history: socio‐ecological mechanisms - Tejas S. Athni; Marta S. Shocket; Lisa I. Couper; Nicole Nova; Iain R. Caldwell; Jamie M. Caldwell; Jasmine N. Childress; Marissa L. Childs; Giulio A. De Leo; Devin G. Kirk; Andrew J. MacDonald; Kathryn Olivarius; et al. (Ecology Letters, 2021)
Vector‐borne diseases (VBDs) are embedded within complex socio‐ecological systems. While research has traditionally focused on the direct effects of VBDs on human morbidity and mortality, it is increasingly clear that their impacts are much more pervasive. VBDs are dynamically linked to feedbacks between environmental conditions, vector ecology, disease burden, and societal responses that drive transmission. As a result, VBDs have had profound influence on human history. Mechanisms include: (1) killing or debilitating large numbers of people, with demographic and population‐level impacts; (2) differentially affecting populations based on prior history of disease exposure, immunity, and resistance; (3) being weaponised to promote or justify hierarchies of power, colonialism, racism, classism and sexism; (4) catalysing changes in ideas, institutions, infrastructure, technologies and social practices in efforts to control disease outbreaks; and (5) changing human relationships with the land and environment. We use historical and archaeological evidence interpreted through an ecological lens to illustrate how VBDs have shaped society and culture, focusing on case studies from four pertinent VBDs: plague, malaria, yellow fever and trypanosomiasis. By comparing across diseases, time periods and geographies, we highlight the enormous scope and variety of mechanisms by which VBDs have influenced human history.

Impacts of sea level rise on future storm-induced coastal inundations over massachusetts coast - Changsheng Chen; Zhaolin Lin; Robert C. Beardsley; Tom Shyka; Yu Zhang; Qichun Xu; Jianhua Qi; Huichan Lin; Danya Xu (Natural Hazards, 2021)

Genetic diversity of ‘Candidatus Liberibacter africanus’ in South Africa based on microsatellite markers - Ronel Roberts; Hong Lin; Gerhard Pietersen (European Journal of Plant Pathology, 2021)
Citrus Greening disease (CG) in South Africa (SA) is associated with the fastidious bacterium ‘ Candidatus Liberibacter africanus’ (Laf). It has been observed that Laf isolates obtained from different geographic localities in SA differed in the rate of transmission during grafting experiments leading to the hypothesis that genetic variation of Laf may exist in this country. To determine this, 167 Laf isolates obtained from Limpopo, North West, Mpumalanga and the Western Cape were subjected to microsatellite analyses, using four polymorphic markers. From UPGMA and STRUCTURE analysis, it was shown that most sources belong to one of two major genetic groups of Laf and these comprise 25 distinct haplotypes. Four samples included within this study did not group with these two major groups, suggesting a potential third and fourth genetic group of Laf being present, which can be validated by further sampling. Results further indicate that Laf populations in SA are formed by geographic locality. The high genetic diversity observed for Laf within this study is consistent with the hypothesis that Laf originated on the African continent, warranting further genetic analysis of Laf populations from Africa. This is the first study to unveil the genetic diversity of Laf.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Mild acidity likely accelerates the physiological matriptase autoactivation process: a comparative study between spontaneous and acid-induced matriptase zymogen activation - Bailing Jia; Hamishi A. Thompson; Robert B. Barndt; Yi-Lin Chiu; Mon-Juan Lee; See-Chi Lee; Jehng-Kang Wang; Hung-Jen Tang; Chen-Yong Lin; Michael D. Johnson (Human Cell, 2020)

A magnetic resonance spectroscopy investigation in symptomatic former NFL players - Michael L. Alosco; Yorghos Tripodis; Benjamin Rowland; Alicia S. Chua; Huijun Liao; Brett Martin; Johnny Jarnagin; Christine E. Chaisson; Ofer Pasternak; Sarina Karmacharya; Inga K. Koerte; Robert C. Cantu; et al. (Brain Imaging and Behavior, 2020)

New evidence for Jurassic continental rifting in the northern Sanandaj Sirjan Zone, western Iran: the Ghalaylan seamount, southwest Ghorveh - Hossein Azizi; Fatemeh Nouri; Robert J. Stern; Marie Azizi; Federico Lucci; Yoshihiro Asahara; Mohammad Hossein Zarinkoub; Sun Lin Chung (International Geology Review, 2020)

Development of a FRET-Based Assay for Analysis of mAbs Internalization and Processing by Dendritic Cells in Preclinical Immunogenicity Risk Assessment - Yi Wen; Suntara Cahya; Wei Zeng; Joanne Lin; Xiaoli Wang; Ling Liu; Laurent Malherbe; Robert Siegel; Andrea Ferrante; Arunan Kaliyaperumal (The AAPS Journal, 2020)

Climate‐induced changes in the suitable habitat of cold‐water corals and commercially important deep‐sea fishes in the North Atlantic - Telmo Morato; José‐Manuel González‐Irusta; Carlos Dominguez‐Carrió; Chih‐Lin Wei; Andrew Davies; Andrew K. Sweetman; Gerald H. Taranto; Lindsay Beazley; Ana García‐Alegre; Anthony Grehan; Pascal Laffargue; Francisco Javier Murillo; et al. (Global Change Biology, 2020)
The deep sea plays a critical role in global climate regulation through uptake and storage of heat and carbon dioxide. However, this regulating service causes warming, acidification and deoxygenation of deep waters, leading to decreased food availability at the seafloor. These changes and their projections are likely to affect productivity, biodiversity and distributions of deep‐sea fauna, thereby compromising key ecosystem services. Understanding how climate change can lead to shifts in deep‐sea species distributions is critically important in developing management measures. We used environmental niche modelling along with the best available species occurrence data and environmental parameters to model habitat suitability for key cold‐water coral and commercially important deep‐sea fish species under present‐day (1951–2000) environmental conditions and to project changes under severe, high emissions future (2081–2100) climate projections (RCP8.5 scenario) for the North Atlantic Ocean. Our models projected a decrease of 28%–100% in suitable habitat for cold‐water corals and a shift in suitable habitat for deep‐sea fishes of 2.0°–9.9° towards higher latitudes. The largest reductions in suitable habitat were projected for the scleractinian coral Lophelia pertusa and the octocoral Paragorgia arborea , with declines of at least 79% and 99% respectively. We projected the expansion of suitable habitat by 2100 only for the fishes Helicolenus dactylopterus and Sebastes mentella (20%–30%), mostly through northern latitudinal range expansion. Our results projected limited climate refugia locations in the North Atlantic by 2100 for scleractinian corals (30%–42% of present‐day suitable habitat), even smaller refugia locations for the octocorals Acanella arbuscula and Acanthogorgia armata (6%–14%), and almost no refugia for P. arborea . Our results emphasize the need to understand how anticipated climate change will affect the distribution of deep‐sea species including commercially important fishes and foundation species, and highlight the importance of identifying and preserving climate refugia for a range of area‐based planning and management tools.

Potential changes to the biology and challenges to the management of invasive sea lamprey Petromyzon marinus in the Laurentian Great Lakes due to climate change - Robert J. Lennox; Gale A. Bravener; Hsien‐Yung Lin; Charles P. Madenjian; Andrew M. Muir; Christina K. Remucal; Kelly F. Robinson; Andrew M. Rous; Michael J. Siefkes; Michael P. Wilkie; Daniel P. Zielinski; Steven J. Cooke (Global Change Biology, 2020)
Control programs are implemented to mitigate the damage caused by invasive species worldwide. In the highly invaded Great Lakes, the climate is expected to become warmer with more extreme weather and variable precipitation, resulting in shorter iced‐over periods and variable tributary flows as well as changes to pH and river hydrology and hydrogeomorphology. We review how climate change influences physiology, behavior, and demography of a damaging invasive species, sea lamprey ( Petromyzon marinus ), in the Great Lakes, and the consequences for sea lamprey control efforts. Sea lamprey control relies on surveys to monitor abundance of larval sea lamprey in Great Lakes tributaries. The abundance of parasitic, juvenile sea lampreys in the lakes is calculated by surveying wounding rates on lake trout ( Salvelinus namaycush ), and trap surveys are used to enumerate adult spawning runs. Chemical control using lampricides (i.e., lamprey pesticides) to target larval sea lamprey and barriers to prevent adult lamprey from reaching spawning grounds are the most important tools used for sea lamprey population control. We describe how climate change could affect larval survival in rivers, growth and maturation in lakes, phenology and the spawning migration as adults return to rivers, and the overall abundance and distribution of sea lamprey in the Great Lakes. Our review suggests that Great Lakes sea lamprey may benefit from climate change with longer growing seasons, more rapid growth, and greater access to spawning habitat, but uncertainties remain about the future availability and suitability of larval habitats. Consideration of the biology of invasive species and adaptation of the timing, intensity, and frequency of control efforts is critical to the management of biological invasions in a changing world, such as sea lamprey in the Great Lakes.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Temporal population variability in local forest communities has mixed effects on tree species richness across a latitudinal gradient - Tak Fung; Ryan A. Chisholm; Kristina Anderson‐Teixeira; Norm Bourg; Warren Y. Brockelman; Sarayudh Bunyavejchewin; Chia‐Hao Chang‐Yang; Rutuja Chitra‐Tarak; George Chuyong; Richard Condit; Handanakere S. Dattaraja; Stuart J. Davies; et al. (Ecology Letters, 2020)
Among the local processes that determine species diversity in ecological communities, fluctuation‐dependent mechanisms that are mediated by temporal variability in the abundances of species populations have received significant attention. Higher temporal variability in the abundances of species populations can increase the strength of temporal niche partitioning but can also increase the risk of species extinctions, such that the net effect on species coexistence is not clear. We quantified this temporal population variability for tree species in 21 large forest plots and found much greater variability for higher latitude plots with fewer tree species. A fitted mechanistic model showed that among the forest plots, the net effect of temporal population variability on tree species coexistence was usually negative, but sometimes positive or negligible. Therefore, our results suggest that temporal variability in the abundances of species populations has no clear negative or positive contribution to the latitudinal gradient in tree species richness.

Adapting to climate change: an assessment of local adaptation planning processes in forest-based communities in Nepal - Pratigya Silwal; Lin Roberts; Hamish G. Rennie; Manfred J. Lexer (Climate and Development, 2019)

Transgenic maize phosphoenolpyruvate carboxylase alters leaf–atmosphere CO2 and 13CO2 exchanges in Oryza sativa - Rita Giuliani; Shanta Karki; Sarah Covshoff; Hsiang-Chun Lin; Robert A. Coe; Nuria K. Koteyeva; Marc A. Evans; W. Paul Quick; Susanne von Caemmerer; Robert T. Furbank; Julian M. Hibberd; Gerald E. Edwards; et al. (Photosynthesis Research, 2019)

Bismuth(III) interactions with Desulfovibrio desulfuricans: inhibition of cell energetics and nanocrystal formation of Bi2S3 and Bi0 - Larry L. Barton; Alex S. Granat; Seungyeol Lee; Huifang Xu; Nathaniel L. Ritz; Robert Hider; Henry C. Lin (BioMetals, 2019)

High‐resolution projections of extreme heat in New York City - Luis E. Ortiz; Jorge E. González; Radley Horton; Wuyin Lin; Wei Wu; Prathap Ramamurthy; Mark Arend; Robert D. Bornstein (International Journal of Climatology, 2019)
Heat waves impact a wide array of human activities, including health, cooling energy demand, and infrastructure. Cities amplify many of these impacts by concentrating large populations and critical infrastructure in relatively small areas. In addition, heat waves are expected to become longer, more intense, and more frequent in North America. Here, we evaluate combined climate and urban surface impacts on localized heat wave metrics throughout the 21st century across two emissions scenarios (RCP4.5 and RCP8.5) for New York City (NYC), which houses the largest urban population in the United States. We account for local biases due to urban surfaces via bias correcting with observed records and urbanized 1‐km resolution dynamical downscaling simulations across selected time periods (2045–2049 and 2095–2099). Analysis of statistically downscaled global model output shows underestimation of uncorrected summer daily maximum temperatures, leading to lower heat wave intensity and duration projections. High‐resolution dynamical downscaling simulations reveal strong dependency of changes in event duration and intensity on geographical location and urban density. Event intensity changes are expected to be highest closer to the coast, where afternoon sea‐breezes have traditionally mitigated summer high temperatures. Meanwhile, event duration anomaly is largest over Manhattan, where the urban canopy is denser and taller.

Long term experimental drought alters community plant trait variation, not trait means, across three semiarid grasslands - Wentao Luo; Xiaoan Zuo; Robert J. Griffin-Nolan; Chong Xu; Wang Ma; Lin Song; Kenny Helsen; Yingchao Lin; Jiangping Cai; Qiang Yu; Zhengwen Wang; Melinda D. Smith; et al. (Plant and Soil, 2019)

Global in situ Observations of Essential Climate and Ocean Variables at the Air–Sea Interface - Luca R. Centurioni; Jon Turton; Rick Lumpkin; Lancelot Braasch; Gary Brassington; Yi Chao; Etienne Charpentier; Zhaohui Chen; Gary Corlett; Kathleen Dohan; Craig Donlon; Champika Gallage; et al. (Frontiers in Marine Science, 2019)

Global Perspectives on Observing Ocean Boundary Current Systems - Robert E. Todd; Francisco P. Chavez; Sophie Clayton; Sophie Cravatte; Marlos Goes; Michelle Graco; Xiaopei Lin; Janet Sprintall; Nathalie V. Zilberman; Matthew Archer; Javier Arístegui; Magdalena Balmaseda; et al. (Frontiers in Marine Science, 2019)

Environment‐ and trait‐mediated scaling of tree occupancy in forests worldwide - Haibao Ren; Petr Keil; Xiangcheng Mi; Keping Ma; Zhanqing Hao; Wanhui Ye; Luxiang Lin; Renato Valencia; Christine Dawn Fletcher; Duncan W. Thomas; Robert W. Howe; James Lutz; et al. (Global Ecology and Biogeography, 2019)
Aim The relationship between the proportion of sites occupied by a species and the area of a site [occupancy–area relationship (OAR)] offers key information for biodiversity management and has long fascinated ecologists. We quantified the variation in OAR for 3,157 woody species in 17 forest plots worldwide and tested the relative importance of environment and species traits for explaining this variation and evaluated overall model predictive ability. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We used mixed‐effect regression to examine the observed shape of the OAR (its “slope”) against species‐specific and plot‐wide predictors: coarse‐grain occupancy, tree size, plot species richness, energy availability and topographic complexity. Results We found large variation in OAR slopes, and the variation was strongest among species within plots. The OAR slopes showed a latitudinal trend and were steeper near the equator. As predicted, coarse‐grain occupancy and tree size negatively affected OAR slopes, whereas species richness had a positive effect and explained most of the variance between plots. Although hypothesized directionalities were broadly confirmed, traits and environment had relatively limited overall predictive power. Main conclusions These results document the variation of the OAR for 3,157 species at near‐global extent. We found a latitudinal gradient in OAR slopes and confirmed key hypothesized predictors. But at this global extent and over the large set of species analysed, the remaining unexplained variation in OAR slopes was substantial. Nevertheless, this large‐scale empirical analysis of the OAR offers an initial step towards a more general use of OARs for the fine‐scale prediction of species distributions and abundance.

Ocean Observations in Support of Studies and Forecasts of Tropical and Extratropical Cyclones - Ricardo Domingues; Akira Kuwano-Yoshida; Patricia Chardon-Maldonado; Robert E. Todd; George Halliwell; Hyun-Sook Kim; I.-I. Lin; Katsufumi Sato; Tomoko Narazaki; Lynn K. Shay; Travis Miles; Scott Glenn; et al. (Frontiers in Marine Science, 2019)

Application of Mechanistic Ocular Absorption Modeling and Simulation to Understand the Impact of Formulation Properties on Ophthalmic Bioavailability in Rabbits: a Case Study Using Dexamethasone Suspension - Maxime Le Merdy; Jianghong Fan; Michael B. Bolger; Viera Lukacova; Jessica Spires; Eleftheria Tsakalozou; Vikram Patel; Lin Xu; Sharron Stewart; Ashok Chockalingam; Suresh Narayanasamy; Rodney Rouse; et al. (The AAPS Journal, 2019)

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Limbic system structure volumes and associated neurocognitive functioning in former NFL players - Christian Lepage; Marc Muehlmann; Yorghos Tripodis; Jakob Hufschmidt; Julie Stamm; Katie Green; Pawel Wrobel; Vivian Schultz; Isabelle Weir; Michael L. Alosco; Christine M. Baugh; Nathan G. Fritts; et al. (Brain Imaging and Behavior, 2019)

Climate of the weakly-forced yet high-impact convective storms throughout the Ohio River Valley and Mid-Atlantic United States - Binod Pokharel; S.-Y. Simon Wang; Jonathan Meyer; Robert Gillies; Yen-Heng Lin (Climate Dynamics, 2019)

The role of heterogeneous environment and docetaxel gradient in the emergence of polyploid, mesenchymal and resistant prostate cancer cells - Ke-Chih Lin; Gonzalo Torga; Yusha Sun; Robert Axelrod; Kenneth J. Pienta; James C. Sturm; Robert H. Austin (Clinical & Experimental Metastasis, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

Gross primary productivity of a large metropolitan region in midsummer using high spatial resolution satellite imagery - David L. Miller; Dar A. Roberts; Keith C. Clarke; Yang Lin; Olaf Menzer; Emily B. Peters; Joseph P. McFadden (Urban Ecosystems, 2018)

Patterns and drivers of species diversity in the Indo‐Pacific red seaweed Portieria - Frederik Leliaert; Dioli Ann Payo; Carlos Frederico D. Gurgel; Tom Schils; Stefano G. A. Draisma; Gary W. Saunders; Mitsunobu Kamiya; Alison R. Sherwood; Showe‐Mei Lin; John M. Huisman; Line Le Gall; Robert J. Anderson; et al. (Journal of Biogeography, 2018)
Aim Biogeographical processes underlying Indo‐Pacific biodiversity patterns have been relatively well studied in marine shallow water invertebrates and fishes, but have been explored much less extensively in seaweeds, despite these organisms often displaying markedly different patterns. Using the marine red alga Portieria as a model, we aim to gain understanding of the evolutionary processes generating seaweed biogeographical patterns. Our results will be evaluated and compared with known patterns and processes in animals. Location Indo‐Pacific marine region. Methods Species diversity estimates were inferred using DNA ‐based species delimitation methods. Historical biogeographical patterns were inferred based on a six‐gene time‐calibrated phylogeny, distribution data of 802 specimens, and probabilistic modelling of geographical range evolution. The importance of geographical isolation for speciation was further evaluated by population genetic analyses at the intraspecific level. Results We delimited 92 candidate species, most with restricted distributions, suggesting low dispersal capacity. Highest species diversity was found in the Indo‐Malay Archipelago ( IMA ). Our phylogeny indicates that Portieria originated during the late Cretaceous in the area that is now the Central Indo‐Pacific. The biogeographical history of Portieria includes repeated dispersal events to peripheral regions, followed by long‐term persistence and diversification of lineages within those regions, and limited dispersal back to the IMA . Main conclusions Our results suggest that the long geological history of the IMA played an important role in shaping Portieria diversity. High species richness in the IMA resulted from a combination of speciation at small spatial scales, possibly as a result of increased regional habitat diversity from the Eocene onwards, and species accumulation via dispersal and/or island integration through tectonic movement. Our results are consistent with the biodiversity feedback model, in which biodiversity hotspots act as both “centres of origin” and “centres of accumulation,” and corroborate previous findings for invertebrates and fish that there is no single unifying model explaining the biological diversity within the IMA .

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Problems of classification in the family Paramyxoviridae - Bert Rima; Peter Collins; Andrew Easton; Ron Fouchier; Gael Kurath; Robert A. Lamb; Benhur Lee; Andrea Maisner; Paul Rota; Lin-Fa Wang (Archives of Virology, 2018)

Genetic and biometric variation across the fragmented range of Jerdon’s Babbler, Chrysomma altirostre, a threatened Oriental grassland specialist - Keren R. Sadanandan; Urban Olsson; Robert Tizard; Aleem A. Khan; Thet Zaw Naing; Naing Lin; Nila Pwint; Frank E. Rheindt (Journal of Ornithology, 2018)

Glycosaminoglycans from bovine eye vitreous humour and interaction with collagen type II - Yanfei Peng; Yanlei Yu; Lei Lin; Xinyue Liu; Xing Zhang; Peipei Wang; Pauline Hoffman; So Young Kim; Fuming Zhang; Robert J. Linhardt (Glycoconjugate Journal, 2018)

Glycosaminoglycans from fish swim bladder: isolation, structural characterization and bioactive potential - Yongxi Pan; Peipei Wang; Fuming Zhang; Yanlei Yu; Xing Zhang; Lei Lin; Robert J. Linhardt (Glycoconjugate Journal, 2018)

Evaluation of toxicity of Deepwater Horizon slick oil on spat of the oyster Crassostrea virginica - Julien Vignier; Anne Rolton; Philippe Soudant; Fu-lin E. Chu; René Robert; Aswani K. Volety (Environmental Science and Pollution Research, 2018)

Effects of Ganoderma Lucidum shell-broken spore on oxidative stress of the rabbit urinary bladder using an in vivo model of ischemia/reperfusion - Robert M. Levin; Li Xia; Wu Wei; Catherine Schuler; Robert E. Leggett; Alpha D.-Y. Lin (Molecular and Cellular Biochemistry, 2017)

Construction and functional characterization of truncated versions of recombinant keratanase II from Bacillus circulans - Haisheng Wang; Wenqin He; Peixia Jiang; Yanlei Yu; Lei Lin; Xiaojun Sun; Mattheos Koffas; Fuming Zhang; Robert J. Linhardt (Glycoconjugate Journal, 2017)

Identification of a seed coat-specific promoter fragment from the Arabidopsis MUCILAGE-MODIFIED4 gene - Gillian H. Dean; Zhaoqing Jin; Lin Shi; Elahe Esfandiari; Robert McGee; Kylie Nabata; Tiffany Lee; Ljerka Kunst; Tamara L. Western; George W. Haughn (Plant Molecular Biology, 2017)

Structural and activity variability of fractions with different charge density and chain length from pharmaceutical heparins - Yanlei Yu; Makoto Hirakane; Daisuke Mori; Lei Lin; Fuming Zhang; Hong Zhang; Robert J. Linhardt (Glycoconjugate Journal, 2017)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

The role of functional uniqueness and spatial aggregation in explaining rarity in trees - María Natalia Umaña; Xiangcheng Mi; Min Cao; Brian J. Enquist; Zhanqing Hao; Robert Howe; Yoshiko Iida; Daniel Johnson; Luxiang Lin; Xiaojuan Liu; Keping Ma; I‐Fang Sun; et al. (Global Ecology and Biogeography, 2017)
Aim Determining the drivers of species rarity is fundamental for understanding and conserving biodiversity. Rarity of a given species within its community may arise due to exclusion by other ecologically similar species. Conversely, rare species may occupy habitats that are rare in the landscape or they may be ill‐suited to all available habitats. The first mechanism would lead to common and rare species occupying similar ecological space defined by functional traits. The second mechanism would result in common and rare species occupying dissimilar ecological space and spatial aggregation of rare species, either because they are specialists in rare habitats or because rare species tend to be dispersal limited. Here, we quantified the contribution of locally rare species to community functional richness and the spatial aggregation of species across tree communities world‐wide to address these hypotheses. Location Asia and the Americas. Time period 2002 to 2012 (period that considers the censuses for the plots used). Major taxa studied Angiosperm and Gymnosperm trees. Methods We compiled a dataset of functional traits from all the species present in eight tree plots around the world to evaluate the contribution of locally rare species to tree community functional richness using multi‐ and univariate approaches. We also quantified the spatial aggregation of individuals within species at several spatial scales as it relates to abundance. Results Locally rare tree species in temperate and tropical forests tended to be functionally unique and are consistently spatially clustered. Furthermore, there is no evidence that this pattern is driven by pioneer species being locally rare. Main conclusions This evidence shows that locally rare tree species disproportionately contribute to community functional richness, and we can therefore reject the hypothesis that locally rare species are suppressed by ecologically similar, but numerically dominant, species. Rather, locally rare species are likely to be specialists on spatially rare habitats or they may be ill‐suited to the locally available environments.

CRISPR-Cas9 and CRISPR-Cpf1 mediated targeting of a stomatal developmental gene EPFL9 in rice - Xiaojia Yin; Akshaya K. Biswal; Jacqueline Dionora; Kristel M. Perdigon; Christian P. Balahadia; Shamik Mazumdar; Caspar Chater; Hsiang-Chun Lin; Robert A. Coe; Tobias Kretzschmar; Julie E. Gray; Paul W. Quick; et al. (Plant Cell Reports, 2017)

Indole signalling and (micro)algal auxins decrease the virulence of V ibrio campbellii , a major pathogen of aquatic organisms - Qian Yang; Gde Sasmita Julyantoro Pande; Zheng Wang; Baochuan Lin; Robert A. Rubin; Gary J. Vora; Tom Defoirdt (Environmental Microbiology, 2017)
Summary Vibrios belonging to the Harveyi clade are major pathogens of marine vertebrates and invertebrates, causing major losses in wild and cultured organisms. Despite their significant impact, the pathogenicity mechanisms of these bacteria are not yet completely understood. In this study, the impact of indole signalling on the virulence of Vibrio campbellii was investigated. Elevated indole levels significantly decreased motility, biofilm formation, exopolysaccharide production and virulence to crustacean hosts. Indole furthermore inhibited the three‐channel quorum sensing system of V. campbellii , a regulatory mechanism that is required for full virulence of the pathogen. Further, indole signalling was found to interact with the stress sigma factor RpoS. Together with the observations that energy‐consuming processes (motility and bioluminescence) are downregulated, and microarray‐based transcriptomics demonstrating that indole decreases the expression of genes involved in energy and amino acid metabolism, the data suggest that indole is a starvation signal in V. campbellii . Finally, it was found that the auxins indole‐3‐acetic acid and indole‐3‐acetamide, which were produced by various (micro)algae sharing the aquatic environment with V. campbellii , have a similar effect as observed for indole. Auxins might, therefore, have a significant impact on the interactions between vibrios, (micro)algae and higher organisms, with major ecological and practical implications.

Myosin II sequences for Lethocerus indicus - Lanette Fee; Weili Lin; Feng Qiu; Robert J. Edwards (Journal of Muscle Research and Cell Motility, 2017)

Tissue Concentration of Dodecafluoropentane (DDFP) Following Repeated IV Administration in the New Zealand White Rabbit - Christine Arthur; Lin Song; William Culp; Aliza Brown; Michael Borrelli; Robert Skinner; Howard Hendrickson (The AAPS Journal, 2017)

Potassium channels in the Cx43 gap junction perinexus modulate ephaptic coupling: an experimental and modeling study - Rengasayee Veeraraghavan; Joyce Lin; James P. Keener; Robert Gourdie; Steven Poelzing (Pflügers Archiv - European Journal of Physiology, 2016)

Effects of probiotics on soil microbial activity, biomass and enzymatic activity under cover crops in field and greenhouse studies - Ahsan M. Rajper; Ranjith P. Udawatta; Robert J. Kremer; Chung-ho Lin; Shibu Jose (Agroforestry Systems, 2016)

Urban high-resolution fossil fuel CO2 emissions quantification and exploration of emission drivers for potential policy applications - Risa Patarasuk; Kevin Robert Gurney; Darragh O’Keeffe; Yang Song; Jianhua Huang; Preeti Rao; Martin Buchert; John C. Lin; Daniel Mendoza; James R. Ehleringer (Urban Ecosystems, 2016)

Cortical thinning in former professional soccer players - Inga K. Koerte; Michael Mayinger; Marc Muehlmann; David Kaufmann; Alexander P. Lin; Denise Steffinger; Barbara Fisch; Boris-Stephan Rauchmann; Stefanie Immler; Susanne Karch; Florian R. Heinen; Birgit Ertl-Wagner; et al. (Brain Imaging and Behavior, 2016)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

Copper(II) binding properties of hepcidin - Kanokwan Kulprachakarn; Yu-Lin Chen; Xiaole Kong; Maria C. Arno; Robert C. Hider; Somdet Srichairatanakool; Sukhvinder S. Bansal (JBIC Journal of Biological Inorganic Chemistry, 2016)

Biogeographic patterns of soil diazotrophic communities across six forests in the North America - Qichao Tu; Ye Deng; Qingyun Yan; Lina Shen; Lu Lin; Zhili He; Liyou Wu; Joy D. Van Nostrand; Vanessa Buzzard; Sean T. Michaletz; Brian J. Enquist; Michael D. Weiser; et al. (Molecular Ecology, 2016)
Soil diazotrophs play important roles in ecosystem functioning by converting atmospheric N 2 into biologically available ammonium. However, the diversity and distribution of soil diazotrophic communities in different forests and whether they follow biogeographic patterns similar to macroorganisms still remain unclear. By sequencing nifH gene amplicons, we surveyed the diversity, structure and biogeographic patterns of soil diazotrophic communities across six North American forests (126 nested samples). Our results showed that each forest harboured markedly different soil diazotrophic communities and that these communities followed traditional biogeographic patterns similar to plant and animal communities, including the taxa–area relationship ( TAR ) and latitudinal diversity gradient. Significantly higher community diversity and lower microbial spatial turnover rates (i.e. z ‐values) were found for rainforests (~0.06) than temperate forests (~0.1). The gradient pattern of TAR s and community diversity was strongly correlated ( r 2 > 0.5) with latitude, annual mean temperature, plant species richness and precipitation, and weakly correlated ( r 2 pH and soil moisture. This study suggests that even microbial subcommunities (e.g. soil diazotrophs) follow general biogeographic patterns (e.g. TAR , latitudinal diversity gradient), and indicates that the metabolic theory of ecology and habitat heterogeneity may be the major underlying ecological mechanisms shaping the biogeographic patterns of soil diazotrophic communities.

Resistance to viral yellow leaf curl in tomato through RNAi targeting two Begomovirus species strains - Huei-mei Chen; Chen-yu Lin; Wen-shi Tsai; Lawrence Kenyon; Ming-tsair Chan; Jo-yi Yen; Shao-yu Chang; Robert de la Peña; Roland Schafleitner (Journal of Plant Biochemistry and Biotechnology, 2016)

Bismuth(III) deferiprone effectively inhibits growth of Desulfovibrio desulfuricans ATCC 27774 - Larry L. Barton; Daniel A. Lyle; Nathaniel L. Ritz; Alex S. Granat; Ali N. Khurshid; Nada Kherbik; Robert Hider; Henry C. Lin (BioMetals, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Stochastic dilution effects weaken deterministic effects of niche‐based processes in species rich forests - Xugao Wang; Thorsten Wiegand; Nathan J. B. Kraft; Nathan G. Swenson; Stuart J. Davies; Zhanqing Hao; Robert Howe; Yiching Lin; Keping Ma; Xiangcheng Mi; Sheng‐Hsin Su; I‐Fang Sun; et al. (Ecology, 2016)
Recent theory predicts that stochastic dilution effects may result in species‐rich communities with statistically independent species spatial distributions, even if the underlying ecological processes structuring the community are driven by deterministic niche differences. Stochastic dilution is a consequence of the stochastic geometry of biodiversity where the identities of the nearest neighbors of individuals of a given species are largely unpredictable. Under such circumstances, the outcome of deterministic species interactions may vary greatly among individuals of a given species. Consequently, nonrandom patterns in the biotic neighborhoods of species, which might be expected from coexistence or community assembly theory (e.g., individuals of a given species are neighbored by phylogenetically similar species), are weakened or do not emerge, resulting in statistical independence of species spatial distributions. We used data on phylogenetic and functional similarity of tree species in five large forest dynamics plots located across a gradient of species richness to test predictions of the stochastic dilution hypothesis. To quantify the biotic neighborhood of a focal species we used the mean phylogenetic (or functional) dissimilarity of the individuals of the focal species to all species within a local neighborhood. We then compared the biotic neighborhood of species to predictions from stochastic null models to test if a focal species was surrounded by more or less similar species than expected by chance. The proportions of focal species that showed spatial independence with respect to their biotic neighborhoods increased with total species richness. Locally dominant, high‐abundance species were more likely to be surrounded by species that were statistically more similar or more dissimilar than expected by chance. Our results suggest that stochasticity may play a stronger role in shaping the spatial structure of species rich tropical forest communities than it does in species poorer forests. These findings represent an important step towards understanding the factors that govern the spatial configuration of local biotic communities. The stochastic dilution effect is a simple geometric mechanism that can explain why species’ spatial distributions in species‐rich communities approximate independence from their biotic neighborhood, even if deterministic niche processes are in effect.

Extracellular sodium and potassium levels modulate cardiac conduction in mice heterozygous null for the Connexin43 gene - Sharon A. George; Katherine J. Sciuto; Joyce Lin; Mohamed E. Salama; James P. Keener; Robert G. Gourdie; Steven Poelzing (Pflügers Archiv - European Journal of Physiology, 2015)

Sodium channels in the Cx43 gap junction perinexus may constitute a cardiac ephapse: an experimental and modeling study - Rengasayee Veeraraghavan; Joyce Lin; Gregory S. Hoeker; James P. Keener; Robert G. Gourdie; Steven Poelzing (Pflügers Archiv - European Journal of Physiology, 2015)

Identification of proteins capable of metal reduction from the proteome of the Gram‐positive bacterium D esulfotomaculum reducens MI ‐1 using an NADH ‐based activity assay - Anne Elyse Otwell; Robert W. Sherwood; Sheng Zhang; Ornella D. Nelson; Zhi Li; Hening Lin; Stephen J. Callister; Ruth E. Richardson (Environmental Microbiology, 2015)
Summary Understanding of microbial metal reduction is based almost solely on studies of G ram‐negative organisms. In this study, we focus on D esulfotomaculum reducens MI ‐1, a G ram‐positive metal reducer whose genome lacks genes with similarity to any characterized metal reductase. Using non‐denaturing separations and mass spectrometry identification, in combination with a colorimetric screen for chelated F e( III )‐ NTA reduction with NADH as electron donor, we have identified proteins from the D . reducens proteome not previously characterized as iron reductases. Their function was confirmed by heterologous expression in E scherichia coli . Furthermore, we show that these proteins have the capability to reduce soluble C r( VI ) and U ( VI ) with NADH as electron donor. The proteins identified are NADH : flavin oxidoreductase ( D red_2421) and a protein complex composed of oxidoreductase flavin adenine dinucleotide/ NAD ( P )‐binding subunit ( D red_1685) and dihydroorotate dehydrogenase 1B ( D red_1686). D red_2421 was identified in the soluble proteome and is predicted to be a cytoplasmic protein. D red_1685 and D red_1686 were identified in both the soluble as well as the insoluble protein fraction, suggesting a type of membrane association, although PSORTb predicts both proteins are cytoplasmic. This study is the first functional proteomic analysis of D . reducens and one of the first analyses of metal and radionuclide reduction in an environmentally relevant G ram‐positive bacterium.

Environmental lead exposure is associated with visit-to-visit systolic blood pressure variability in the US adults - Mohammed F. Faramawi; Robert Delongchamp; Yu-Sheng Lin; Youcheng Liu; Saly Abouelenien; Lori Fischbach; Supriya Jadhav (International Archives of Occupational and Environmental Health, 2015)

Mechanisms underlying local functional and phylogenetic beta diversity in two temperate forests - Xugao Wang; Thorsten Wiegand; Nathan G. Swenson; Amy T. Wolf; Robert W. Howe; Zhanqing Hao; Fei Lin; Ji Ye; Zuoqiang Yuan (Ecology, 2015)
Although trait information has been widely used to explore underlying mechanisms of forest community structure, most studies have focused on local patterns of phylogenetic or functional alpha diversity. Investigations of functional beta diversity, on the other hand, have not been conducted at local scales in a spatially explicit way. In this study, we provide a powerful methodology based on recent advances in spatial point pattern analysis using fully mapped data of large and small trees in two large temperate forest plots. This approach allowed us to assess the relative importance of different ecological processes and mechanisms for explaining patterns of local phylogenetic and functional beta diversity. For both forests and size classes, we found a clear hierarchy of scales: habitat filtering accounted for patterns of phylogenetic and functional beta diversity at larger distances (150–250 m), dispersal limitation accounted for the observed decline in beta diversity at distances below 150 m, and species interactions explained small departures from functional and phylogenetic beta diversity at the immediate plant‐neighborhood scale (below 20 m). Thus, both habitat filtering and dispersal limitation influenced the observed patterns in phylogenetic and functional beta diversity at local scales. This result contrasts with a previous study from the same forests, where dispersal limitation alone approximated the observed species beta diversity for distances up to 250 m. In addition, species interactions were relatively unimportant for predicting phylogenetic and functional beta diversity. Our analysis suggests that phylogenetic and functional beta diversity can provide insights into the mechanisms of local community assembly that are missed by studies focusing exclusively on species beta diversity.

Genetic variation in estrogen and progesterone pathway genes and breast cancer risk: an exploration of tumor subtype-specific effects - Sarah J. Nyante; Marilie D. Gammon; Jay S. Kaufman; Jeannette T. Bensen; Dan Yu Lin; Jill S. Barnholtz-Sloan; Yijuan Hu; Qianchuan He; Jingchun Luo; Robert C. Millikan (Cancer Causes & Control, 2015)

Asterixis: a study of 103 patients - Gian Pal; Mark M. Lin; Robert Laureno (Metabolic Brain Disease, 2014)

Effects of Parkinson’s disease on optic flow perception for heading direction during navigation - Cheng-Chieh Lin; Robert C. Wagenaar; Daniel Young; Elliot L. Saltzman; Xiaolin Ren; Sandy Neargarder; Alice Cronin-Golomb (Experimental Brain Research, 2014)

An ecological function and services approach to total maximum daily load (TMDL) prioritization - Robert K. Hall; David Guiliano; Sherman Swanson; Michael J. Philbin; John Lin; Joan L. Aron; Robin J. Schafer; Daniel T. Heggem (Environmental Monitoring and Assessment, 2014)

Exosomes from human adipose-derived mesenchymal stem cells promote migration through Wnt signaling pathway in a breast cancer cell model - Ruizhu Lin; Shihua Wang; Robert Chunhua Zhao (Molecular and Cellular Biochemistry, 2013)

Effect of aging on inter-joint synergies during machine-paced assembly tasks - Xu Xu; Jin Qin; Robert D. Catena; Gert S. Faber; Jia-Hua Lin (Experimental Brain Research, 2013)

Nyamiviridae: Proposal for a new family in the order Mononegavirales - Jens H. Kuhn; Sadia Bekal; Yíngyún Caì; Anna N. Clawson; Leslie L. Domier; Marieke Herrel; Peter B. Jahrling; Hideki Kondo; Kris N. Lambert; Kathie A. Mihindukulasuriya; Norbert Nowotny; Sheli R. Radoshitzky; et al. (Archives of Virology, 2013)

Electrophysiological and behavioral responses to ketamine in mice with reduced Akt1 expression - Robert E. Featherstone; Valerie M.Tatard-Leitman; Jimmy D. Suh; Robert Lin; Irwin Lucki; Steven J. Siegel (Psychopharmacology, 2013)

Synthesis, physico-chemical properties, and antimicrobial evaluation of a new series of iron(III) hexadentate chelators - Yuan-Yuan Xie; Mu-Song Liu; Pan-Pan Hu; Xiao-Le Kong; Di-Hong Qiu; Ji-Lin Xu; Robert C. Hider; Tao Zhou (Medicinal Chemistry Research, 2013)

Size of TiO2 nanoparticles influences their phototoxicity: an in vitro investigation - Sijing Xiong; Saji George; Zhaoxia Ji; Sijie Lin; Haiyang Yu; Robert Damoiseaux; Bryan France; Kee Woei Ng; Say Chye Joachim Loo (Archives of Toxicology, 2013)

Integrate-and-fire vs Poisson models of LGN input to V1 cortex: noisier inputs reduce orientation selectivity - I-Chun Lin; Dajun Xing; Robert Shapley (Journal of Computational Neuroscience, 2012)

Human Health Risk Assessment of 16 Priority Polycyclic Aromatic Hydrocarbons in Soils of Chattanooga, Tennessee, USA - Erika Hussar; Sean Richards; Zhi-Qing Lin; Robert P. Dixon; Kevin A. Johnson (Water, Air, & Soil Pollution, 2012)

Disease-modifying drugs for multiple sclerosis and JC virus expression - Craig S. Miller; Sidney A. Houff; Jason Hopper; Robert J. Danaher; Julie A. Gurwell; Yushun Lin; Nubia Vega; Joseph R. Berger (Journal of NeuroVirology, 2012)

FVCOM model estimate of the location of Air France 447 - Changsheng Chen; Richard Limeburner; Guoping Gao; Qichun Xu; Jianhua Qi; Pengfei Xue; Zhigang Lai; Huichan Lin; Robert Beardsley; Breck Owens; Barry Carlson (Ocean Dynamics, 2012)

Chronic traumatic encephalopathy: neurodegeneration following repetitive concussive and subconcussive brain trauma - Christine M. Baugh; Julie M. Stamm; David O. Riley; Brandon E. Gavett; Martha E. Shenton; Alexander Lin; Christopher J. Nowinski; Robert C. Cantu; Ann C. McKee; Robert A. Stern (Brain Imaging and Behavior, 2012)

Excitation energy transfer and trapping dynamics in the core complex of the filamentous photosynthetic bacterium Roseiflexus castenholzii - Yueyong Xin; Jie Pan; Aaron M. Collins; Su Lin; Robert E. Blankenship (Photosynthesis Research, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Bait worm packaging as a potential vector of invasive species - Christina L. Haska; Charles Yarish; George Kraemer; Noreen Blaschik; Robert Whitlatch; Huan Zhang; Senjie Lin (Biological Invasions, 2012)

Liposomes Containing (-)-Gossypol-Enriched Cottonseed Oil Suppress Bcl-2 and Bcl-xL Expression in Breast Cancer Cells - Hong Li; Longzhu Piao; Pingping Xu; Weiping Ye; Saiyi Zhong; Shu-Hong Lin; Samuel K. Kulp; Yicheng Mao; Youngah Cho; L. James Lee; Robert J. Lee; Young C. Lin (Pharmaceutical Research, 2011)

The Business of Forest Enterprise / Urban Ecosystems / Forest Policy / Biosecurity - David Nicholls; Allen Brackley; Charles Keegan; Colin Sorenson; Jean Daniels; Erik Berg; Charles Gale; Robert Campbell; Charles Gale; Charles Keegan; Erik Berg; Colin Sorenson; et al. (Journal of Forestry, 2011)
172Business clusters are geographic concentrations of companies that provide mutual advantages for their participants. Clusters can include diverse members including competitors, customers, partners, and/or suppliers. In Alaska, wood products business clusters can have unique challenges associated with remote locations, high raw material costs, limited local markets, and potentially long transportation distances. Further, multiple land ownership near communities (for example state versus federal ownership) can influence raw material procurement, since different administrative processes for timber harvesting may be required. This study evaluates 2 resource dependent communities in southeast Alaska (Haines, AK and Craig, AK), seeking to identify elements that could enhance their potential for wood products clusters and new business formation. We consider how the flow of forest resources, from harvest to finished product, can influence local communities and either enhance or limit opportunities for wood products businesses. We evaluate the effect of various product mixes—including firewood, woody residues, house logs, lumber, and secondary wood products—on the composition, scale, and dynamics of wood products firms. We consider the effect of harvesting practices and proximity to timber sales in evaluating how land ownership can influence the viability of wood products clusters. Lastly we consider the impact of transportation costs on serving local and export markets. Our research builds upon past work in Alaska that evaluated national-forest based communities in Alaska, finding opportunities for greater innovation, higher productivity, and greater social well-being associated with wood products clusters.

Gold Nanoparticle Penetration and Reduced Metabolism in Human Skin by Toluene - Hagar I. Labouta; David C. Liu; Lynlee L. Lin; Margaret K. Butler; Jeffrey E. Grice; Anthony P. Raphael; Tobias Kraus; Labiba K. El-Khordagui; H. Peter Soyer; Michael S. Roberts; Marc Schneider; Tarl W. Prow (Pharmaceutical Research, 2011)

Time-Correlated Single Photon Counting For Simultaneous Monitoring Of Zinc Oxide Nanoparticles And NAD(P)H In Intact And Barrier-Disrupted Volunteer Skin - Lynlee L. Lin; Jeffrey E. Grice; Margaret K. Butler; Andrei V. Zvyagin; Wolfgang Becker; Thomas A. Robertson; H. Peter Soyer; Michael S. Roberts; Tarl W. Prow (Pharmaceutical Research, 2011)

A multivalent vaccine for type 1 diabetes skews T cell subsets to Th2 phenotype in NOD mice - Ming S. Lin; Hubert M. Tse; Meghan M. Delmastro; Suzanne Bertera; Caterina T. Wong; Robert Lakomy; Jing He; Martha M. Sklavos; Gina M. Coudriet; Massimo Pietropaolo; Massimo M. Trucco; Jon D. Piganelli (Immunologic Research, 2011)

A novel statistical method for classifying habitat generalists and specialists - Robin L. Chazdon; Anne Chao; Robert K. Colwell; Shang-Yi Lin; Natalia Norden; Susan G. Letcher; David B. Clark; Bryan Finegan; J. Pablo Arroyo (Ecology, 2011)
We develop a novel statistical approach for classifying generalists and specialists in two distinct habitats. Using a multinomial model based on estimated species relative abundance in two habitats, our method minimizes bias due to differences in sampling intensities between two habitat types as well as bias due to insufficient sampling within each habitat. The method permits a robust statistical classification of habitat specialists and generalists, without excluding rare species a priori. Based on a user‐defined specialization threshold, the model classifies species into one of four groups: (1) generalist; (2) habitat A specialist; (3) habitat B specialist; and (4) too rare to classify with confidence. We illustrate our multinomial classification method using two contrasting data sets: (1) bird abundance in woodland and heath habitats in southeastern Australia and (2) tree abundance in second‐growth (SG) and old‐growth (OG) rain forests in the Caribbean lowlands of northeastern Costa Rica. We evaluate the multinomial model in detail for the tree data set. Our results for birds were highly concordant with a previous nonstatistical classification, but our method classified a higher fraction (57.7%) of bird species with statistical confidence. Based on a conservative specialization threshold and adjustment for multiple comparisons, 64.4% of tree species in the full sample were too rare to classify with confidence. Among the species classified, OG specialists constituted the largest class (40.6%), followed by generalist tree species (36.7%) and SG specialists (22.7%). The multinomial model was more sensitive than indicator value analysis or abundance‐based phi coefficient indices in detecting habitat specialists and also detects generalists statistically. Classification of specialists and generalists based on rarefied subsamples was highly consistent with classification based on the full sample, even for sampling percentages as low as 20%. Major advantages of the new method are (1) its ability to distinguish habitat generalists (species with no significant habitat affinity) from species that are simply too rare to classify and (2) applicability to a single representative sample or a single pooled set of representative samples from each of two habitat types. The method as currently developed can be applied to no more than two habitats at a time.

Chronic exposure to ambient particulate matter alters cardiac gene expression patterns and markers of oxidative stress in rats - Boris Z. Simkhovich; Michael T. Kleinman; Ruty Mehrian-Shai; Ya-Hsuan Hsu; Dianne Meacher; Glenn Gookin; Michael Mac Kinnon; Karina Salazar; Paul Willet; Gang Feng; Simon M. Lin; Robert A. Kloner (Air Quality, Atmosphere & Health, 2011)

In Vitro–In Vivo Correlations of Scalable PLGA-Risperidone Implants for the Treatment of Schizophrenia - Laura C. Amann; Michael J. Gandal; Robert Lin; Yuling Liang; Steven J. Siegel (Pharmaceutical Research, 2010)

Exposure to water increased pollen longevity of pondweed (Potamogeton spp.) indicates different mechanisms ensuring pollination success of angiosperms in aquatic habitat - Xiao-lin Zhang; Robert W. Gituru; Chun-feng Yang; You-hao Guo (Evolutionary Ecology, 2010)

Dopaminergic neurotoxicity following pulmonary exposure to manganese-containing welding fumes - Krishnan Sriram; Gary X. Lin; Amy M. Jefferson; Jenny R. Roberts; Rebecca S. Chapman; Bean T. Chen; Joleen M. Soukup; Andrew J. Ghio; James M. Antonini (Archives of Toxicology, 2010)

Genetic variation in sex-steroid receptors and synthesizing enzymes and colorectal cancer risk in women - Jennifer Lin; Robert Y. L. Zee; Kuang-Yu Liu; Shumin M. Zhang; I-Min Lee; JoAnn E. Manson; Edward Giovannucci; Julie E. Buring; Nancy R. Cook (Cancer Causes & Control, 2010)

Angiotensin IV elevates oxytocin levels in the rat amygdala and produces anxiolytic-like activity through subsequent oxytocin receptor activation - Chad E. Beyer; Jason M. Dwyer; Brian J. Platt; Sarah Neal; Bin Luo; Huai-Ping Ling; Qian Lin; Robert J. Mark; Sharon Rosenzweig-Lipson; Lee E. Schechter (Psychopharmacology, 2010)

Assessing the prospects of genome-wide association studies performed in inbred mice - Wan-Lin Su; Solveig K. Sieberts; Robert R. Kleinhanz; Karine Lux; Joshua Millstein; Cliona Molony; Eric E. Schadt (Mammalian Genome, 2010)

Impact of female cigarette smoking on circulating B cells in vivo: the suppressed ICOSLG, TCF3, and VCAM1 gene functional network may inhibit normal cell function - Feng Pan; Tie-Lin Yang; Xiang-Ding Chen; Yuan Chen; Ge Gao; Yao-Zhong Liu; Yu-Fang Pei; Bao-Yong Sha; Yan Jiang; Chao Xu; Robert R. Recker; Hong-Wen Deng (Immunogenetics, 2010)

Modulation of prostate cancer cell gene expression by cell-to-cell contact with bone marrow stromal cells or osteoblasts - Shuming Zhang; Jun Wang; Mehmet A. Bilen; Sue-Hwa Lin; Samuel I. Stupp; Robert L. Satcher (Clinical & Experimental Metastasis, 2009)

A note on reviving the Goddard Satellite-based Surface Turbulent Fluxes (GSSTF) dataset - Chung-Lin Shie; Long S. Chiu; Robert Adler; Eric Nelkin; I. -I. Lin; Pingping Xie; Feng-Chin Wang; R. Chokngamwong; William Olson; D. Allen Chu (Advances in Atmospheric Sciences, 2009)

An Overview of Global Observing Systems Relevant to GODAE - Candyce Clark; D.E. Harrison; Mike Johnson; Graeme Ball; Howard Freeland; Gustavo Goni; Maria Hood; Michael McPhaden; David Meldrum; Mark Merrifield; Dean Roemmich; Chris Sabine; et al. (Oceanography, 2009)

Provenance and thermal history of the Bayan Har Group in the western‐central Songpan–Ganzi–Bayan Har terrane: Implications for tectonic evolution of the northern Tibetan Plateau - Guo‐Can Wang; Robert P. Wintsch; John I. Garver; Mary Roden‐Tice; She‐Fa Chen; Ke‐Xin Zhang; Qi‐Xiang Lin; Yun‐Hai Zhu; Shu‐Yuan Xiang; De‐Wei Li (Island Arc, 2009)
Triassic turbidites dominate the Songpan–Ganzi–Bayan Har (SGBH) terrane of the northern Tibetan Plateau. U‐Pb dating on single detrital zircon grains from the Triassic Bayan Har Group turbidites yield peaks at 400–500 m.y., 900–1000 m.y., 1800–1900 m.y., and 2400–2500 m.y., These results are consistent with recently published U‐Pb zircon ages of pre‐Triassic bedrock in the East Kunlun, Altyn, Qaidam, Qilian and Alaxa areas to the north, suggesting that provenance of the Bayan Har Group may include these rocks. The similarities in the compositions of the lithic arkosic sandstones of the Bayan Har Group with the sandstones of the Lower‐Middle Triassic formations in the East Kunlun terrane to the north also suggests a common northern provenance for both. A well exposed angular unconformity between the Carboniferous–Middle Permian mélange sequences and the overlying Upper Permian or Triassic strata indicates that regional deformation occurred between the Middle and Late Permian. This deformation may have been the result of a soft collision between the Qiangtang terrane and the North China Plate and the closure of the Paleo‐Tethyan oceanic basin. The Bayan Har Group turbidites were then deposited in a re‐opened marine basin on a shelf environment. Fission‐track dating of detrital zircons from the Bayan Har Group sandstones revealed pre‐ and post‐depositional age components, suggesting that the temperatures did not reach the temperatures necessary to anneal retentive zircon fission tracks (250–300°C). A 282–292 m.y. peak age defined by low U concentration, retentive zircons likely reflects a northern granitic source. Euhedral zircons from two lithic arkoses with abundant volcanic fragments in the southern area yielded a ∼237 m.y. zircon fission track (ZFT) peak age, likely recording the maximum age of deposition. A dominant post‐depositional 170–185 m.y. ZFT peak age suggests peak temperatures were reached in the Early Jurassic. Some samples appear to record a younger thermal event at ∼140 m.y., a short lived event that apparently affected only the least retentive zircons.

Comparison of human post-embryonic, multipotent stem cells derived from various tissues - Baijun Fang; Ning Li; Yongping Song; Quande Lin; Robert Chunhua Zhao (Biotechnology Letters, 2009)

Sufficient sampling for asymptotic minimum species richness estimators - Anne Chao; Robert K. Colwell; Chih-Wei Lin; Nicholas J. Gotelli (Ecology, 2009)
Biodiversity sampling is labor intensive, and a substantial fraction of a biota is often represented by species of very low abundance, which typically remain undetected by biodiversity surveys. Statistical methods are widely used to estimate the asymptotic number of species present, including species not yet detected. Additional sampling is required to detect and identify these species, but richness estimators do not indicate how much sampling effort (additional individuals or samples) would be necessary to reach the asymptote of the species accumulation curve. Here we develop the first statistically rigorous nonparametric method for estimating the minimum number of additional individuals, samples, or sampling area required to detect any arbitrary proportion (including 100%) of the estimated asymptotic species richness. The method uses the Chao1 and Chao2 nonparametric estimators of asymptotic richness, which are based on the frequencies of rare species in the original sampling data. To evaluate the performance of the proposed method, we randomly subsampled individuals or quadrats from two large biodiversity inventories (light trap captures of Lepidoptera in Great Britain and censuses of woody plants on Barro Colorado Island [BCI], Panama). The simulation results suggest that the method performs well but is slightly conservative for small sample sizes. Analyses of the BCI results suggest that the method is robust to nonindependence arising from small‐scale spatial aggregation of species occurrences. When the method was applied to seven published biodiversity data sets, the additional sampling effort necessary to capture all the estimated species ranged from 1.05 to 10.67 times the original sample (median ≈ 2.23). Substantially less effort is needed to detect 90% of the species (0.33–1.10 times the original effort; median ≈ 0.80). An Excel spreadsheet tool is provided for calculating necessary sampling effort for either abundance data or replicated incidence data.

Acid sensing ion channel (ASIC) inhibitors exhibit anxiolytic-like activity in preclinical pharmacological models - Jason M. Dwyer; Stacey J. Sukoff Rizzo; Sarah J. Neal; Qian Lin; Flora Jow; Robert L. Arias; Sharon Rosenzweig-Lipson; John Dunlop; Chad E. Beyer (Psychopharmacology, 2009)

Ligand-induced nuclear translocation of S1P1 receptors mediates Cyr61 and CTGF transcription in endothelial cells - Rosendo Estrada; Lichun Wang; Venkatakrishna R. Jala; Jen-Fu Lee; Cheng-Yon Lin; Robert D. Gray; Bodduluri Haribabu; Menq-Jer Lee (Histochemistry and Cell Biology, 2009)

The impact of chemical lateral boundary conditions on CMAQ predictions of tropospheric ozone over the continental United States - Youhua Tang; Pius Lee; Marina Tsidulko; Ho-Chun Huang; Jeffery T. McQueen; Geoffrey J. DiMego; Louisa K. Emmons; Robert B. Pierce; Anne M. Thompson; Hsin-Mu Lin; Daiwen Kang; Daniel Tong; et al. (Environmental Fluid Mechanics, 2009)

Coenzyme Q10 protect against ischemia/reperfusion induced biochemical and functional changes in rabbit urinary bladder - Yung-Shun Juan; Tasmina Hydery; Anita Mannikarottu; Barry Kogan; Catherine Schuler; Robert E. Leggett; Wei-Yu Lin; Chun-Hsiung Huang; Robert M. Levin (Molecular and Cellular Biochemistry, 2008)

Release of intracellular Zn2+ in cultured neurons after brief exposure to low concentrations of exogenous nitric oxide - Wei Lin; Bhavana Mohandas; Charles P. Fontaine; Robert A. Colvin (BioMetals, 2007)

Effect of aging on the response of biochemical markers in the rabbit subjected to short-term partial bladder obstruction - Ahmet Guven; Wei-Yu Lin; Robert E. Leggett; Barry A. Kogan; Robert M. Levin; Anita Mannikarottu (Molecular and Cellular Biochemistry, 2007)

Immuno-localization of vesicular acetylcholine transporter in mouse taste cells and adjacent nerve fibers: indication of acetylcholine release - Tatsuya Ogura; Robert F. Margolskee; Yvonne N. Tallini; Bo Shui; Michael I. Kotlikoff; Weihong Lin (Cell and Tissue Research, 2007)

Conservation of Heathland Ground Beetles (Coleoptera, Carabidae): The Value of Lowland Coniferous Plantations - Ying-Chi Lin; Robert James; Paul M. Dolman (Biodiversity and Conservation, 2007)

Effect of bilateral in vivo ischemia/reperfusion on the activities of superoxide dismutase and catalase: Response to a standardized grape suspension - Alpha Dian-Yu Lin; Anita Mannikarottu; Barry A. Kogan; Catherine Whitbeck; Robert E. Leggett; Robert M. Levin (Molecular and Cellular Biochemistry, 2007)

Cytotoxic kurubasch aldehyde from Trichilia emetica - Maminata Traore; Lin Zhai; Ming Chen; Carl Erik Olsen; Nacoulma Odile; Guissou I. Pierre; Ouédrago J. Bosco; Guigemdé T. Robert; S. Brøgger Christensen (Natural Product Research, 2007)

Introgression mapping in the grasses - Julie King; Ian P. Armstead; Iain S. Donnison; John A. Harper; Luned A. Roberts; Howard Thomas; Helen Ougham; Ann Thomas; Lin Huang; Ian P. King (Chromosome Research, 2007)

Association analyses of CYP19 gene polymorphisms with height variation in a large sample of Caucasian nuclear families - Tie-Lin Yang; Dong-Hai Xiong; Yan Guo; Robert R. Recker; Hong-Wen Deng (Human Genetics, 2006)

BCRP Transports Dipyridamole and is Inhibited by Calcium Channel Blockers - Yi Zhang; Anshul Gupta; Honggang Wang; Lin Zhou; R. Robert Vethanayagam; Jashvant D. Unadkat; Qingcheng Mao (Pharmaceutical Research, 2005)

Purification and Characterization of the B808–866 Light-harvesting Complex from Green Filamentous Bacterium Chloroflexus aurantiacus - Yueyong Xin; Su Lin; Gabriel A. Montaño; Robert E. Blankenship (Photosynthesis Research, 2005)

Spectral and Kinetic Analysis of the Energy Coupling in the PS I–LHC I Supercomplex from the Green Alga Chlamydomonas reinhardtii at 77 K - Alexander N. Melkozernov; Joanna Kargul; Su Lin; James Barber; Robert E. Blankenship (Photosynthesis Research, 2005)

Heavy Metals in Wastewater: The Effect of Electrolyte Composition on the Precipitation of Cadmium(II) Using Lime and Magnesia - Xiaomei Lin; Robert C. Burns; Geoffrey A. Lawrance (Water, Air, & Soil Pollution, 2005)

Clinical and electrophysiological characterization of a novel mutation R863X in HERG C-terminus associated with long QT syndrome - Siyong Teng; Lijuan Ma; Yingxue Dong; Chunxia Lin; Jue Ye; Robert Bhring; Vitya Vardanyan; Yanzong Yang; Zhihu Lin; Olaf Pongs; Rutai Hui (Journal of Molecular Medicine, 2004)

A general map matching algorithm for transport telematics applications - Mohammed A. Quddus; Washington Yotto Ochieng; Lin Zhao; Robert B. Noland (GPS Solutions, 2003)

Disruption of plE2, the gene for the E2 subunit of the plastid pyruvate dehydrogenase complex, in Arabidopsis causes an early embryo lethal phenotype - Ming Lin; Robert Behal; David J. Oliver (Plant Molecular Biology, 2003)

Effect of Cadmium(Ii) and Anion Type on the Ageing of Ferrihydrite and its Subsequent Leaching under Neutral and Alkaline Conditions - Xiaomei Lin; Robert C. Burns; Geoffrey A. Lawrance (Water, Air, & Soil Pollution, 2003)

Deregulated activation of matriptase in breast cancer cells - Christelle M. Benaud; Michael Oberst; Robert B. Dickson; Chen-Yong Lin (Clinical & Experimental Metastasis, 2002)

Stable cell lines expressing baculovirus P35: Resistance to apoptosis and nutrient stress, and increased glycoprotein secretion - Guangyun Lin; Guoxun Li; Robert R. Granados; Gary W. Blissard (In Vitro Cellular & Developmental Biology - Animal, 2001)

STABLE CELL LINES EXPRESSING BACULOVIRUS P35: RESISTANCE TO APOPTOSIS AND NUTRIENT STRESS, AND INCREASED GLYCOPROTEIN SECRETION - GUANGYUN LIN; GUOXUN LI; ROBERT R. GRANADOS; GARY W. BLISSARD (In Vitro Cellular & Developmental Biology - Animal, 2001)

Alcohol Consumption and Breast Cancer among Black and White Women in North Carolina (United States) - Anita Yeomans Kinney; Robert C. Millikan; Yu Hua Lin; Patricia G. Moorman; Beth Newman (Cancer Causes & Control, 2000)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Models of corundum origin from alkali basaltic terrains: a reappraisal - F. Lin Sutherland; Paul W. O. Hoskin; C. Mark Fanning; Robert R. Coenraads (Contributions to Mineralogy and Petrology, 1998)

Molecular cloning and chromosomal mapping of type one serine/threonine protein phosphatases in Arabidopsis thaliana - Qing Lin; Jia Li; Robert D. Smith; John C. Walker (Plant Molecular Biology, 1998)

Characterization of 12 microsatellite loci of the human MHC in a panel of reference cell lines - Maureen P. Martin; Anita Harding; Robert Chadwwick; Mel Kronick; Michael Cullen; Ling Lin; Emmanuel Mignot; M. Carrington (Immunogenetics, 1998)

Characterization of 12 microsatellite loci of the human MHC in a panel of reference cell lines - Maureen P. Martin; Anita Harding; Robert Chadwick; Mel Kronick; Michael Cullen; Ling Lin; Emmanuel Mignot; M. Carrington (Immunogenetics, 1997)

Diversity associated with the second expressed H L A - D R B locus in the human population - FuMeei Robbins; Carolyn Katovich Hurley; Ting Tang; Hanlong Yao; Y. S. Lin; Judy Wade; Nancy Goeken; Robert J. Hartzman (Immunogenetics, 1997)

Distribution of charged pterins in nonmethanogenic archaebacteria - Xinli Lin; Robert H. White (Archives of Microbiology, 1988)

Mutants of Rhizobium japonicum defective in nodulation - Gary Stacey; Alan S. Paau; K. Dale Noel; Robert J. Maier; Lin E. Silver; Winston J. Brill (Archives of Microbiology, 1982)